An intelligent model predictive control method for pressurized water reactor power control - Qichang Huang; Zhi Chen; Yin Luo; Yunxin Miao; Bo Wan (Annals of Nuclear Energy, 2026)

Synchronous Paleo-Tethys closure in northern Iran: Constraints from Paleozoic-Mesozoic sediments in the western Alborz - Yiyang Lei; Yang Chu; Mark B. Allen; Wei Lin; Bo Wan; Ling Chen; Morteza Talebian; Guangyao Xin; Tanjie Liu; Yilin Guo; Lin Guo; Ranran Xia (Journal of Asian Earth Sciences, 2026)

Causality-preserving short-term cooling-load forecasting with online correction for building cooling systems - Dongdong Li; Yizhe Wang; Yunwei Shen; Can Wan; Shunfu Lin; Bo Zhou (International Journal of Refrigeration, 2026)

Complexation-assisted nanofiltration for high-flux concentration and anti-scaling separation of rare-earth leachates - Xinmiao Hu; Lulu Liu; Yinyan Wang; Bo Peng; Hui Yu; Hongwei Lu; Weijie Song; Yinhua Wan; Jianquan Luo (Chemical Engineering Journal, 2026)

Macro-micro responses of ice-wedge loess subjected to freeze-thaw cycles - Qian-qian Ma; Wan-jun Ye; Zhi-yuan Xu; Tian-qi Song; Yu-bo Zhu; Jian-bing Peng (Cold Regions Science and Technology, 2026)

Exploiting interspecies interactions in a Corynebacterium–Shewanella co-culture improves succinic acid production - Zeng-Wan Deng; Bo Xu; Ming-Hou Li; Dong-Lai Fang; Xin-Qing Zhao; Kai Li (Bioresource Technology, 2026)

Phenylbutene dimers and saturated phenylbutene derivatives from Zingiber montanum with anti-inflammatory potential - Zhi-hang Wu; Lu Chen; Jin-na Zhao; Lv-you Wan; Fa-xiang Guo; Lei Zhang; Li-bo Wang; Jin-hui Wang; Xian-mei Piao (Phytochemistry, 2026)

Polystyrene microplastics induce auditory neurotoxicity in mammals: Integrated multi-omics profiling reveals oxidative damage and synaptic molecular dysregulation - Huanzhi Wan; Jingchun Liu; Xuan Yu; Ting Li; Wenting Yu; Bo Liu; Yingzhao Liu; Yuanyuan Zhang; Shimin Zong; Qingquan Hua; Hongjun Xiao (Journal of Hazardous Materials, 2026)

Assessing and utilizing hydrothermal geothermal resources in a deep mine: a case study of Pingdingshan coalfield, China - Zheng Zhen; Kun Yu; Zhijun Wan; Yiwen Ju; Zhenzi Yu; Liangliang Jiang; Zhuting Wang; Bo Zhang; Zhehan Sun; Peng Shi (Bulletin of Engineering Geology and the Environment, 2026)

The Mesozoic and Early Cenozoic stratigraphy and palaeontology of the Qinghai-Xizang Plateau and adjacent regions - Sha Li; Tian Jiang; Bo Wang; Xiao-Qiao Wan (Palaeoworld, 2026)

Transport Pathway Evolution and Retention Dynamics of Escherichia Coli in Homogeneous and Heterogeneous Porous Media - Yuanyuan Jia; Zhipeng Tu; Wenjing Zhang; Shutong Jiang; Jiaming Sun; Bo Wan (Transport in Porous Media, 2026)

Comparative analysis of heat stress responses in the Korean endemic Hosta minor and H. yingeri - Bo Kyeong Kang; Wan Soon Kim (Horticulture, Environment, and Biotechnology, 2026)

Pseudofrenelopsis (Cheirolepidiaceae) from the Lower Cretaceous of northwestern China and its paleoclimatic and biogeographic significances - Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Cretaceous Research, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Toward high-precision, low-consumption bulk analysis: advancements in extraterrestrial sample studies - Ding-Shuai Xue; Shun Guo; Yan-Hong Liu; Dan-Ping Zhang; Yong-Gang Yao; Bo Wan; Xian-Hua Li (Science Bulletin, 2026)

Ventilation-driven microbial and antimicrobial resistance divergence in intensive poultry houses and the associated public health risks - Xiaojie Wan; Jingjing Zhan; Zhuo Chen; Bo Wu (Research in Veterinary Science, 2026)

Waste cooking oil biodiesel alters combustion pathways to enhance volatile organic compound emissions and reduce intermediate/semi -volatile organic compounds in agricultural machinery - Fan Zhang; Bo Huang; Junfeng Cui; Yi Wang; Xinyi Wan; Lele Han; Gehui Wang; Yong Han; Yu Wang; Hai Guo; Min Cui (Journal of Hazardous Materials, 2026)

Interpretable machine learning-augmented quantitative targeted flavoromics for quality grade prediction of Jiangxiangxing baijiu - Youlan Sun; Lili Jiang; Xiaolong You; Hongbo Luo; Xiaochun Zhu; Luqin Tian; Lan Wu; Hu Lu; Jianfeng Hu; Feng Hu; Bo Wan (Food Research International, 2026)

Flavour changes and quality evolution of pork patties during fat reduction via modified microwave equipment - Fengli Lian; Jinbao Yang; Hongju He; Yangli Wan; Xianqing Huang; Bo Li (Food Research International, 2026)

Electrophysiological and Behavioral Responses of Tuta absoluta to the Tomato-Associated Volatile 1-Nonanol - Weifeng Wang; Bo Xu; Xiaolan Ou; Yanhui Lu; Jingsong Kong; Guifen Zhang; Cong Huang; Yibo Zhang; Fanghao Wan (Neotropical Entomology, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Expression and ligand-binding characterization of two chemosensory proteins (TabsCSP8 and TabsCSP19) in Tuta absoluta - Bo Xu; Lei He; Yanan Zhou; Xiaobing He; Guohui Zhang; Khalid Haddi; Jordi Riudavets; Judit Arnó; Guifen Zhang; Cong Huang; Yibo Zhang; Fanghao Wan (Pesticide Biochemistry and Physiology, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

The red rice wine and its function evaluation based on Caenorhabditis elegans - Feiyue Tao; Gang Zheng; Lihua Zhou; Zhiyu Liu; Changbao Hu; Kuan Gao; Bo Yu; Xiangyong Wang; Cuixiang Wan; Huahong Yu; Zhihua Wu (Journal of Cereal Science, 2026)

Weathering of skarn deposits offsets decarbonation during Jurassic-Cretaceous mineralization in East Asia - Wei Liu; Xu Chu; Wenrong Cao; Bo Wan (Geochimica et Cosmochimica Acta, 2026)

A relic slow-spreading ridge preserved beneath the western Makran forearc basin in Iran - Haiqiang Lan; Ling Chen; Bo Wan; Morteza Talebian; Sebastien Chevrot; Yang Chu; Xu Wang; Jie Chen; Yifan Gao; Zimu Wu; Naeim Mousavi; Xi Xu; et al. (Earth and Planetary Science Letters, 2026)

Lithospheric and atmospheric state shifts controlled the global distribution of iron oxide-apatite (IOA) deposits - Shengchao Yan; Bo Wan; John Mavrogenes; Ulf B. Andersson (Earth-Science Reviews, 2026)

Three-Dimensional Numerical Simulation of Near-Field Hydrodynamic Response and Suspended Sediment Transport Characteristics Around the Caofeidian Port Breakwaters - Yong-Qiang Zhang; Zhe Feng; Cong-Bo Xiong; Wan-Qing Chi; Wan-Jun Zhang (Journal of Marine Science and Engineering, 2026)
Breakwater construction at meso-tidal ports fundamentally alters near-field hydrodynamics and drives harbor sedimentation, yet the three-dimensional mechanisms linking entrance geometry to sediment flux remain poorly quantified. Here, we apply a validated Delft3D tidal–sediment coupled model to Caofeidian Port, Bohai Bay, comparing pre-construction baseline conditions against four entrance width scenarios (400, 300, 250, and 200 m). Breakwater enclosure reduces depth-averaged harbor velocities by 61.9–63.2% during spring tides, while generating tip-jet velocities of 1.41–1.53 m s−1 at the eastern breakwater head—exceeding pre-construction maxima by 14–18%. The eastern tip produces an ebb vortex (radius ~230 m; peak vorticity 0.034 s−1) approximately 34% larger and 62% more intense than its flood counterpart, driving vortex-assisted sediment recirculation toward the harbor interior despite ebb-dominant background velocities. Reynolds flux decomposition confirms that the eastern tip-vortex sector contributes ~39% of net sediment import (advective component: −0.7%), directly quantifying vortex-assisted recirculation as an independent transport mechanism. Bed shear stress falls below the critical erosion threshold (τce = 0.22 Pa) across 76.8% of the harbor area during spring tides (robust lower bound ~60% under wave-coupling correction), creating a structurally stable depositional interior, while the near-entrance zone sustains persistent tidal-cycle resuspension. Asymmetric tidal pumping—flood-phase open-sea SSC of 0.088 kg m−3 versus ebb-phase harbor SSC of 0.032–0.041 kg m−3—drives net spring-tide sediment import of 14.8 × 106 kg per cycle (wave-coupled upper bound: 17.8–19.2 × 106 kg per cycle). Entrance width reduction from 400 to 300 m achieves a favorable sedimentation-to-water exchange trade-off (marginal efficiency ratio 1.23), whereas further reduction to 200 m indicates onset of hydraulic choking. The marginal efficiency ratio declines sharply from 1.23 (400 → 300 m) to 1.03 (300 → 250 m) to 1.01 (250 → 200 m), indicating a hydraulic transition within the 250–300 m range that warrants targeted refinement in future studies.

Residual Content Impacts Critical Quality Attributes and Performance of Risperidone Microspheres - Saurabh Bhorkade; Bo Wan; Pawan Kumar Pandey; Sia Dhruva; Diane Burgess (Pharmaceutical Research, 2026)

Functional trait diversity in overstorey and understorey increases microbial carbon use efficiency in a forest plantation soil - Renping Wan; Junxi Hu; Huan Xiao; Zhe Li; Jingnan Xu; Bo He; Lanlan Song; Lifeng Wang; Jian Peng; Xiaoyan Yu; Xiaolin Li; Lihua Tu; et al. (Soil Biology and Biochemistry, 2026)

Reconstruction of atmospheric CO2 concentration changes during the Aalenian (Middle Jurassic) based on fossil cuticles of Ginkgoites and Czekanowskia from northwestern China - Yu Jiang; Rui-Qi Lou; Yi-Fan Liang; Bo-Jin Gou; Wan-Yu Huang; Jing-Yu Wu; Su-Ting Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Speciated full-volatility organic compound emissions from typical agriculture machinery in China - Yi Wang; Lele Han; Bo Huang; Xia Xu; Xinyi Wan; Yubao Chen; Yong Han; Min Cui; Yu Wang; Hai Guo; Fan Zhang; Gehui Wang (Journal of Environmental Sciences, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

Open spatial relation extraction about geological objects with dependency graph network - Deping Chu; Lele Fu; Bo Wan; Fang Fang; Shunping Zhou (Earth Science Informatics, 2026)

Dynamic monitoring of dark slope streaks within large-scale Martian scenes using multitemporal high-resolution orbiter imagery - Bo Wan; Sicong Liu; Xiaohua Tong; Huan Xie; Yongjiu Feng; Yanmin Jin; Kecheng Du; Jie Zhang (Advances in Space Research, 2026)

Decoding the core microbiota during liquor fermentation of sauce-aroma baijiu: Advances in the characteristics of core microbial communities and their regulatory strategies - Cheng Wu; Xiuting Li; Bo Wan; Feng Hu; Jianfeng Hu; Hu Lu; Xi Chen; Weiwei Li; Diqiang Wang; Baoguo Sun (Food Research International, 2026)

Sonoporation-mediated bioremediation of DNAPLs: A synergistic approach integrating phase redistribution and genetic augmentation - Xiaoyang Wang; Wenjing Zhang; Juanfen Chai; Zhechao Hua; Hongyu Zhao; Shuxin Li; Bo Wan (Environmental Research, 2026)

Checkpointing-Assisted Automatic Differentiation Full Waveform Inversion - Jian Sun; Chunwang Jin; Xiaolei Wan; Bo Du; Ying Liu; Xiangfeng Geng (Journal of Ocean University of China, 2026)

Unlocking potent oxidase-like activity in bimetallic MnCo-MOFs: A nanozyme-based immunoassay for rapid detection of a Lumpy skin disease virus protein - Mingzhu Wang; Yuanjie Deng; Zixiang Zhu; Chengru Zhou; Bo Wan; Lingjie Meng; Hong Tian; Yanxin Wang; Haixue Zheng; Xiaoping Zhao (Analytica Chimica Acta, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Physiologically Based Pharmacokinetic (PBPK) Modeling of Oral Drug Absorption for Integrating Nonclinical Data into Human Pharmacokinetic Predictions - Xiaomin Liang; Grace Fraczkiewicz; Krutika Meena Harish Jain; Bo Wan; Kazuya Ishida; Yurong Lai (The AAPS Journal, 2026)

Design of the head assembly scheme for the pressure-retaining drilling tool of the seafloor drill and analysis of the flow performance of the valve assembly - Zhigang Xu; Jialiang Wang; Bo Li; Buyan Wan; Mengfei Yu; Siqi Hu (Marine Georesources & Geotechnology, 2026)

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

PPAR subtypes determine distinct modes of action of phthalate esters (PAEs) and per- and polyfluoroalkyl substances (PFAS) in disrupting human macrophage alternative activation - Zhisen Zhuang; Lijuan You; Jianbo Kong; Yaru Tian; Yongning Li; Yuan Zhi; Bo Zhang; Yi Wan; Xudong Jia; Hui Yang (Toxicology, 2026)

Analyzing the impact of urban morphology on urban land surface temperature from the perspective of spatial configuration and explainable machine learning: A case study of seven cities - Bo Wan; Ningjie Shen; Haijian Zhang; Qiang Sheng (Sustainable Cities and Society, 2026)

From management to regeneration: A skin-inspired biomimetic dressing for the full-cycle care of diabetic wounds - Yingjie Lu; Lianglong Chen; Bo Liu; Yuanlin Zeng; Jiangbo Wan (Chemical Engineering Journal, 2026)

Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

PEDV nonstructural protein 14 inhibits RIPK3 and RIPK1-mediated PANoptosis - Xingyi Xie; Dengkun Wang; Xueke Sun; Xuechen Li; Mengru Luo; Jiahao Cong; Wenju Yuan; Huihui Huang; Zhaojiang Chen; Yuhang Zhang; Zhengjie Kong; Bo Wan (Veterinary Microbiology, 2026)

Palynological succession in Gzhelian No. 8 Thick Coal of the Taiyuan Formation, Ordos Basin, North China - Hui Zhang; Yun-He Shi; Peng-Shuai Jiao; Bo Pan; Feng Liu; Ming-Li Wan; Jing-Kun Zhang; Hui-Ping Peng (Palaeoworld, 2026)

Quantitative interface-specific deposition mechanisms of pathogenic microorganisms and nanoplastics in variable saturation zone - Bo Wan; Wenjing Zhang; Xiaotao Hong; Zhipeng Tu; Shuxin Li; Juanfen Chai (Journal of Hydrology, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Hydrophilic tripeptide L-glutathione enhanced methane hydrate formation with high energy density and rapid methane uptake: implications for gas storage - Qing-Cui Wan; Yuan-Le Li; Bo Li; Gui-Cai Li; Xin-Miao Liu (Chemical Engineering Journal, 2026)

Membrane stability under heat stress: molecular signaling, lipid remodeling, and defense mechanisms in plants - Bo Chen; Yu Wang; Yumin Zhu; Jia Li; Lingyun Wan; Chaoyang Zhu; Qiulan Huang; Mohamed A. Abd Elhamid; Salma A. Soaud; Kuan Yan; Ahmed H. El-Sappah (Plant Cell Reports, 2026)

CD95 ligand drives abdominal aortic aneurysm progression through Caspase-8-mediated GSDMD-dependent endothelial pyroptosis: modulation by SRC kinase - Tian-tian Ke; Chuan Yuan; Yong Yuan; Jin-long Liu; Xue-liang Zhou; Ji-chun Liu; Wan-fen Xiong; Zhi-bo Liu (Apoptosis, 2026)

Clinochinsaponin A, a triterpenoid saponin from the aerial parts of Clinopodium chinense - Xin-hua Hu; Dong-ying Zhao; Jing Hu; Xin-yu Zang; Wan-shan Chen; Bai-bo Xie; Wen-peng Yuan (Natural Product Research, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Seawater-convective dolomitization linked to the passive–active continental margin transition during the Ordovician in the western Ordos Basin, North China - Feifan Lu; Kaibo Shi; Liubin Wei; Bo Liu; Yanlin Liang; Zhaole Wan; Haofu Zheng; Ying Bai; Jiuyuan Wang; Yixin Dong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of neutral and alkaline salt stress on seed germination, physiological and biochemical properties of Andrographis paniculata (Burm.f.) Wall. ex Nees - Ming Zhang; Kai-xuan Shi; Jia Jiang; Qiao-chu Ma; Wan-bo Ding; Qing-ni Peng; Ya-ping Shi; Mei-long Liu; Zhi Sun; Ming Li; Sheng Wang (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Geothermal energy accumulation mechanism and development mode in a deep mine: A case study - Zheng Zhen; Kun Yu; Zhijun Wan; Yiwen Ju; Zhenzi Yu; Zhuting Wang; Bo Zhang; Peng Shi; Zhehan Sun; Jiakun Lv (Geothermics, 2026)

Flavor characteristics of traditional and mechanically processed base baijiu of sauce-flavor baijiu revealed by GC-IMS and GC-MS - Ruiqi Liu; Jialiang Niu; Bo Wan; Feng Hu; Cheng Wu; Junlin Yang; Anran Zhu; Baoguo Sun; Xiuting Li (Food Chemistry, 2026)

Highly permeable acid-resistant nanofiltration membranes for metallurgical spent acid treatment: Structure–performance relationships and selective separation mechanisms - Lichao Teng; Jia Shi; Hui Yu; Enqing Liu; Bo Peng; Hongwei Lu; Weijie Song; Yinhua Wan; Jianquan Luo (Desalination, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Shifts in epidemic patterns and age dynamics of RSV, IFV, and SARS-CoV-2 in Chinese children following COVID-19 non-pharmaceutical intervention relaxation, 2017 − 2024 - Yiguo Zhou; Jian-Bo Xia; Meimei Luo; Wan-Xue Zhang; Shan-Shan Zhang; Le Ao; Han Yang; Qin-Yi Ma; Juan Du; Yu-Ting Wang; Ninghua Huang; Xing-Wen Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Deciphering the causes of getting lost in complex urban space: A multi-scale examination of spatial environmental indicators using multi-source data - Lin Yang; Mingxia Luo; Zejun Zuo; Mei-Po Kwan; Daping Xi; Bo Wan; Shunping Zhou (Applied Geography, 2026)

Genome-wide Characterization of Heat Shock Protein (HSP) Genes in Tuta (Phthorimaea) Absoluta: Insights into Thermal Stress Response - Bo Xu; DeYuan Kong; Guohui Zhang; Cong Huang; Guifen Zhang; Fanghao Wan (Neotropical Entomology, 2025)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Development of a power prediction model for rotary tillage in paddy loam field using DEM-MBD coupling method - Bo-Min Bae; Min-Seung Kim; Se-O Choi; Yeon-Soo Kim; Wan-Soo Kim; Yong-Joo Kim (Computers and Electronics in Agriculture, 2025)

Adenosine signaling in the habenula: a depression-myocardial infarction nexus - Lei Zhang; Mengge Chu; Cailing Ji; Yawen Zhang; Guojia Wan; Bo Du; Xiaowei Chen; Tianhuan Peng; Lilei Yu; Weihong Tan; Jie Tan; Quan Yuan (Science Bulletin, 2025)

Transcriptomic and metabolomic analyses reveal the impact of 1-methylcyclopropene on bitter gourd fruit storage - Feng Guan; Bo Shi; Xuetong Yang; Yuanyuan Xie; Xinjian Wan (Postharvest Biology and Technology, 2025)

Hydrological–geochemical controls on seasonal rare earth element dynamics in semi-arid mining riparian zones: Implications for sustainable remediation - Xuemei Wang; Jie Tang; Guo Liu; Mingtan Zhu; Qianye Wan; Bo Li; Dongping Yang; JinJin Wang; Wanming Zhang; Jinzhao Hu (Journal of Environmental Chemical Engineering, 2025)

Impact of CO2 on sulfur concentration at sulfide saturation in silicate melts: implication for deep Earth sulfur cycling - Kang Liu; Bo Wang; Wan-Cai Li; Huaiwei Ni (Geochimica et Cosmochimica Acta, 2025)

Genome-Wide Identification and Characterization of the Trihelix Transcription Factor Family in Polygonatum kingianum and Gene Expression Pattern Analysis Under MeJA Treatment - Chun-Yu Chen; Wan-Bo Ding; Hong-Jing Zhang; Yan-Ran Qi; Wen-Xiang Wang (Plant Molecular Biology Reporter, 2025)

Identification of the STY13 gene family across the entire genome and an analysis of the essential function of GhSTY13-12 in cotton’s response to abiotic stress - Shaoliang Zhang; Huiyun Shan; Xiaopei Bo; Jiahui Li; Zili Liu; Pengtao Li; Yuling Liu; Xiaojie Yang; Quanwei Lu; Sumei Wan; Renhai Peng; Yangyang Wei; et al. (Functional & Integrative Genomics, 2025)

LLM-GeoCWS: a semi-supervised chinese word segmentation method using large language model for geoscience domain - Deping Chu; Zhuo Tan; Bo Wan; Fang Fang; Shunping Zhou; Yuanjian Zhu; Mingqing Zhu; Yan Wu (Earth Science Informatics, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

A novel framework for multi-step water level predicting by spatial–temporal deep learning models based on integrated physical models - Shuo Zhang; Da Zhang; Guoxian Huang; Jiaquan Wan; Yan Kang; Dongqing Jiang; Bo Xia; Zhonglin Zhao; Ranyu Liu (Journal of Hydrology, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

The multitasking of humic substances: Challenges and opportunities in sustainable water management - Chuan-Ming Xing; Tian Lan; Yuan-Di Ma; Bo Yan; Qing-Lian Wu; Hua-Zhe Wang; Juan-Shan Du; Wan-Qian Guo (Chemical Engineering Journal, 2025)

Evolution of surface ozone pollution in Yangtze Rriver Delta between 2019 and 2022: influences of meteorology and emissions - Ying Zhang; Fenfen Zhang; Mei Wan; Yu Bo; Kebin He; Rui Liu (Atmospheric Environment, 2025)

Vismodegib Potentiates Marine Antimicrobial Peptide Tilapia Piscidin 4-Induced Cytotoxicity in Human Non-Small Cell Lung Cancer Cells - Wei-Chen Yeh; Yun-Chieh Tu; Tzu-Cheng Chien; Pei-Ling Hsu; Chu-Wan Lee; Shih-Ying Wu; Bo-Syong Pan; Hsin-Hsien Yu; Bor-Chyuan Su (Probiotics and Antimicrobial Proteins, 2025)

Combination of ligand‑based and structure‑based virtual screening for the discovery of novel Janus kinase 2 inhibitors against philadelphia-negative myeloproliferative neoplasms - Binyou Wang; Jianmin Guo; Bo Chen; Yan Jiao; Ying Wan; Jianming Wu; Yiwei Wang (Molecular Diversity, 2025)

Unravelling the mechanisms underlying marine redox shifts during sedimentary manganese metallogenesis: insights from the Carboniferous Muhu deposit, China - Zhi-Guo Dong; Bang-Lu Zhang; Lian-Chang Zhang; Fei-Yu Dong; Jie Li; Zi-Dong Peng; Bo Wan; Chang-Le Wang (Mineralium Deposita, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

HARN-LiDAR: hybrid attention-regularized neural LiDAR novel view synthesis - Liucheng Zhang; Jinbo Qie; Shiwei Gao; Bo Liang; Zhibo Wan (International Journal of Remote Sensing, 2025)

A novel partial mRNA-derived duplication of the DMD gene identified in NGS carrier screening - Xue Zhang; Gang Wang; Yuan Wan; Yanling Dong; Daru Lu; Bo Tan (Journal of Genetics, 2025)

ChpR-displaying bacteria for bioremediation of chlorpyrifos and TCP: A whole-cell biosorbent approach - Yan Guo; Can Wu; Shun-yu Hu; Yu-xuan Xie; Wan-yan Wu; Bo-xin Li; Yu-ting Chen; Chang-ye Hui (Water Research, 2025)

Anti-inflammatory abietane-type diterpenoids from the roots of Salvia przewalskii - Yan-Fang Chen; Yu-Qing Lu; Wan-Yun Gao; Bo-Yi Fan; Fu-Cai Ren; Chuan-Pu Shen (Phytochemistry, 2025)

Human activity driven spatial heterogeneity of pollutants in a highland river basin revealed by non-target screening and improved PBT evaluation: A case study from the Yalong River on the Qinghai-Tibet Plateau,China - Zhiyuan Ma; Shunlong Meng; Xin Gao; Hui Wan; Longxiang Fang; Lei Zhu; Zhonghua Li; Yuxiao Gao; Liping Qiu; Bo Rong; Chao Song (Journal of Hazardous Materials, 2025)

Response of PM2.5 concentration to climate variability and climate change prediction in China - Wan Li; Hujia Zhao; Changshuang Wang; Peng Wang; Dong Han; Chengyu Wang; Wenjing Yuan; Shuanglu Bo (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Ultra-stretchable and subzero-healable epidermal electrodes enabled by kirigami-networked microcrack engineering for human-machine interactions - Ying Xiao; Yilu Cui; Jie Wan; Yang Yang; Xiangrong Shi; Lingui Han; Ziming Wang; Dianpeng Qi; Bo Jiang; Kuiyuan Zhang (Chemical Engineering Journal, 2025)

Effects of fertilizers on arsenic accumulation in ratoon rice: implications for human health risks - Kai-Wei Juang; Han-Ting Hsu; Wan-Ting Chiao; Chien-Hui Syu; Bo-Ching Chen (Environmental Geochemistry and Health, 2025)

Corrigendum to "Peganutonin A, a novel melatonin analogue from the seeds of Peganum harmala" [Phytochem. Lett. 56 (2023) 78–80] - Jian-Bo Liu; Wan-Ying Li; Xue Zhao; Feng-Ying Yang; Lei Fang (Phytochemistry Letters, 2025)

Real-time detection of plasmin activity in milk using an ordered porous layer interferometry - Liming Liu; Lu Wang; Ning Ma; Yu Zhang; Yi-Zhen Wan; Tianze Wang; Bo Zhang; Qianqian Su; Shaohua Ding; Weiping Qian (Food Chemistry, 2025)

Thermally stabilized polyacrylonitrile for flexible triboelectric devices operating from −29 °C to 400 °C - Yide Zheng; Rongfeng Mao; Beilei Liu; Bo Ma; Wei Li; Yue Sun; Wan Shou (Chemical Engineering Journal, 2025)

Impact of Clay Minerals on the Characteristic Strength and Nonlinear Dissipative Energy Modeling of Water-Saturation Mudstone - Yugang Cheng; Rui Wu; Bo Hu; Mengru Zeng; Yong Zhao; Gexin Wan; Xuefu Zhang; Jinjie Yang (Rock Mechanics and Rock Engineering, 2025)

Exploring mechanisms of radiation-induced myocardial fibrosis using HMGB1 neutralizing antibody - Gang Wang; Bi-Bo Wu; Sha-Sha Zhao; Jing Zhang; Yu Wang; Yin-Xiang Hu; Jun Wan; Bing Lu; Sheng-Fa Su (Journal of Molecular Histology, 2025)

Senecavirus A nonstructural protein 3A Inhibits Ago2-mediated RNAi antiviral response - Mengru Luo; Xingyi Xie; Dengkun Wang; Xuechen Li; Xianghui Ling; Wenju Yuan; Jiahao Cong; Huihui Huang; Yuhang Zhang; Zhengjie Kong; Bo Wan (Veterinary Microbiology, 2025)

Mitigation of the toxic effects of nitrite: Role and mechanism of isoleucine in mitigating mitochondrial DNA leakage-induced inflammation in grass carp (Ctenopharyngodon idella) under nitrite exposure - Kai-Xuan Ren; Lin Feng; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Cheng-Bo Zhong; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2025)

Rapid formation of high-energy-density methane hydrates promoted by L-cysteine: A promising approach for solidified natural gas - Bo Li; Yuan-Le Li; Xin-Miao Liu; Ting-Ting Zhang; Qing-Cui Wan; Gui-Cai Li (Gas Science and Engineering, 2025)

Enhanced ecological risks of pollutant-adsorbed engineered environmental particles to soil microorganisms - Quan Chen; Yue Zhang; Wan-Rong Zhang; Yu Huang; Min Wu; Hong-Zhe Li; Yi-Yue Zhang; Yi-Fei Wang; Dong Zhu; Philippe Frangois-Xavier Corvini; Bo Pan (Chemical Engineering Journal, 2025)

Enhancing xylose fermentation to maximize net energy gain of lime-pretreated wheat straw by delayed fed-batch simultaneous saccharification and fermentation - Wan-ying Qiu; Chengyu Dong; Jing-jing Guo; Bo Xia; Lujiang Xu; Zhen Fang (Biomass and Bioenergy, 2025)

Novel mechanisms for selenite biotransformation and selenium nanoparticles biogenesis in Acinetobacter sp. SX5 isolated from seleniferous soil - Sheng-Wei Huang; Yuan-yuan Yao; Hua-xu Zhang; Wan-ying Guo; Ming-hui Fang; Hai-bo Wang; Yu-jun Sun; Ming-hao Li (Journal of Hazardous Materials, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

Insights into changes in crust formation mechanisms across the Archean-Proterozoic Transition: Receiver function observations in the Capricorn Orogen, Western Australia - Tingzi Li; Liang Zhao; Jianfeng Yang; Xiaobing Xu; Kun Wang; Bo Wan; Ruth Murdie; Klaus Gessner; Simon Johnson; Huaiyu Yuan (Science China Earth Sciences, 2025)
The transition from the Archean to Proterozoic marks a critical period in Earth’s tectonic history, where primary crustal formation mechanisms may have shifted from vertical-accretion mantle plume tectonics to horizontal-accretion modern-style plate tectonics. Seismological evidence suggests that this regime shift might have left imprints in the crust of stable regions. However, due to sparse spatial and temporal sampling, there is no global consensus on whether seismic observations can infer the secular evolution of crustal characteristics. In this study, we utilized a dense seismic array deployed in the Capricorn Orogen of the West Australian Craton. By analyzing teleseismic receiver functions, we characterized the crustal V P / V S ratio and interface features across approximately two billion years of Archean to Proterozoic craton crust and correlated these observations with the two-stage Nd age model of surficial rocks. Our results indicate that during the Mesoarchean to Paleoproterozoic, crustal thickness in the Capricorn Orogen gradually increased. The changes of V P / V S ratio suggest a crustal evolution from felsic to more intermediate compositions, and the Moho gradient evolves from sharp to gradational. Significant crustal thickening and mafic compositions were observed along major block boundaries, accompanied by weak Moho amplitudes, and asymmetrically dipping Moho, spatially correlating with the Ophthalmia Orogeny (∼2.2 Ga) and the Glenburgh Orogeny (∼2.0 Ga). We propose that these changes in the crustal characteristic initially originated during these two collisional orogenies and were further modified by post-collision thermal and deformational events. Similar features are evident in seismic observations across many Precambrian subduction zones. Thus, we infer that around 2.2 to 2.0 billion years ago, primary crustal formation mechanisms in the West Australian Craton had transitioned to horizontal accretion modern plate tectonics. This study reveals the geometrical characteristics of Neoarchean to Paleoproterozoic subduction, providing new deep constraints for understanding the Archean-Proterozoic crustal accretion and geodynamic regime transitions.

Targeted Screening of Fiber Degrading Bacteria with Probiotic Function in Herbivore Feces - Benhao Chen; Yan Zeng; Jie Wang; Mingxia Lei; Baoxing Gan; Zhiqiang Wan; Liqian Wu; Guangrong Luo; Suizhong Cao; Tianwu An; Qibin Zhang; Kangcheng Pan; et al. (Probiotics and Antimicrobial Proteins, 2025)

Construction of the relationship between phytochemicals and gene expression in different Chaenomeles speciosa (Sweet) Nakai cultivars - Ya-Fang Shang; Jun-Hao Miao; Jia Zeng; Si-Qi Sun; Xiao-Long Ni; Zhao-Jun Wei; Yi-Long Ma; Hong-Xing Su; Wen-Bo Bai; Xiang-Li Niu; Wan Zhang (South African Journal of Botany, 2025)

Municipal sludge as precursors in Chinese medicinal herbal residues composting for plant-growth biostimulant production: Priming effects and microbial mechanism - Chuan-Ming Xing; Yong-Yao Zhang; Yi-Fei Zhang; Yu-Fei Meng; Qing-Lian Wu; Bo Yan; Yao-Hua Wu; Hua-Zhe Wang; Juan-Shan Du; Wan-Qian Guo (Resources, Conservation and Recycling, 2025)

Expression and sex pheromone-binding characteristics of pheromone-binding protein 3 in Tuta absoluta (Lepidoptera: Gelechiidae) - Xiaolan Ou; Xianya Li; Bo Xu; Yusheng Wang; Guifen Zhang; Wanxue Liu; Fanghao Wan; Hongbo Jiang; Khalid Haddi; Cong Huang; Yibo Zhang (Pesticide Biochemistry and Physiology, 2025)

An integrated machine learning framework using borehole descriptions for 3D lithological modeling - Deping Chu; Bo Wan; Yiyang Liu; Lulan Li; Hong Li; Fang Fang; Shengwen Li; Shengyong Pan; Min Wang (Engineering Geology, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Provenance of North Indian geoid ridge and its implication to collision evolution between India and Eurasia - Peilong Yan; Nan Zhang; Xi Liu; Bo Wan (Earth and Planetary Science Letters, 2025)

Monitoring the insecticide susceptibility of a newly introduced invasive species, Tuta absoluta (Meyrick), in China - Yi-bo Zhang; Han Li; Peng Han; Xiao-cao Tian; Hao Wang; Li-li Geng; Jie Zhang; Wan-xue Liu; Fang-hao Wan; Raul-Narciso Guedes; Desneux Nicolas; Gui-fen Zhang (Crop Protection, 2025)

The key role of tyrosinase in color variation of the autotetraploid Carassius auratus - Xi-Dan Xu; Wan-Jing Peng; Yue Zhou; Chong-Qing Wang; Kun Zhang; Xu Huang; Xiao-Wei Xu; Jin-Hai Bai; Ling Xiong; Zheng-Kun Liu; Xin-Yi Deng; Yan Tang; et al. (Aquaculture, 2025)

Tanshinone IIA mitigates postoperative cognitive dysfunction in aged rats by inhibiting hippocampal inflammation and ferroptosis: Role of Nrf2/SLC7A11/GPX4 axis activation - Yan Yang; Bo Wang; Yichen Jiang; Wan Fu (NeuroToxicology, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Resveratrol Protects Müller Cells Against Ferroptosis in the Early Stage of Diabetic Retinopathy by Regulating the Nrf2/GPx4/PTGS2 Pathway - Yi Wang; Si-Yuan Song; Yi Song; Yuan Wang; Zheng-Wei Wan; Ping Sun; Xue-Mei Yu; Bo Deng; Kai-Hong Zeng (Molecular Neurobiology, 2025)

Dual function of the Tuta absoluta 3-phosphoinositide-dependent protein kinase-1 in pupa ecdysis and adult reproduction - Shu-Yan Yan; Jia-Hui Song; Wen-Jia Yang; Wan-xue Liu; Gui-Fen Zhang; Fang-Hao Wan; Nicolas Desneux; Yi-Bo Zhang (Journal of Pest Science, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Theaflavin-3,3′-digallate (TF3) attenuated constipation by promoting gastrointestinal motility and modulating the gut microbiota: A comparative study of TF3 and the anti-constipation drug mosapride in mice - Tingbo Wu; Mingxue Yang; Leyi Jin; Haonan Yu; Haitao Huang; Yuanyuan Wu; Bo Li; Youying Tu; Xiaochun Wan; Junsheng Liu (Food Chemistry, 2025)

Application of 18β-glycyrrhetinic acid in the structural modification of natural products: a review - Wan-Xin Li; Ye-Fang Lu; Fei Wang; Bing Ai; Sheng-Bo Jin; Siqi Li; Guang-Hua Xu; Cheng-Hua Jin (Molecular Diversity, 2025)

Formation and evolution of supercritical geofluid - Huaiwei Ni; Yilin Xiao; Xiaolin Xiong; Xiandong Liu; Chunxiao Gao; Yi-Xiang Chen; Yunguo Li; Wan-Cai Li; Xuan Guo; Yang-Yang Wang; Dong-Bo Tan; Li Zhang (Science China Earth Sciences, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Soil infiltration mechanisms under plant root disturbance in arid and semi-arid grasslands and the response of solute transport in rhizosphere soil - Yuanyuan Jia; Huan Huan; Wenjing Zhang; Bo Wan; Jiaming Sun; Zhipeng Tu (Science of The Total Environment, 2024)

The novel prognostic analysis of AML based on ferroptosis and cuproptosis related genes - Mei Wu; Anan Li; Tingting Zhang; Weirong Ding; Yujing Wei; Caishui Wan; Bo Ke; Hongbo Cheng; Chenghao Jin; Chunfang Kong (Journal of Trace Elements in Medicine and Biology, 2024)

Automatic extraction of Transverse Aeolian Ridges (TARs) and analysis of landform influence for the Zhurong landing area on Mars - Jie Zhang; Sicong Liu; Kecheng Du; Xiaohua Tong; Huan Xie; Yongjiu Feng; Yanmin Jin; Yizhang Lin; Bo Wan (Geomorphology, 2024)

Interface engineering of Platinum–Copper alloy/titanium dioxide for enhanced photocatalytic carbon dioxide reduction - Xin Wang; Wei Tan; Bo Peng; Shangcong Sun; Xue Li; Kaiqiang Wang; Jiawei Ji; Haohong Liao; Jingfang Sun; Qing Tong; Haiqin Wan; Lin Dong (Environmental Research, 2024)

Yeast-enhanced activated sludge for improved nitrogen removal in wastewater treatment: Focus on dissolved organic nitrogen degradation - Pengfei Wan; Ying Liu; Bo Li; Xiao Yu; Li Jiang; Wenzhou Lv (Environmental Research, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Advances on the Mechanisms and Therapeutic Strategies in Non-coding CGG Repeat Expansion Diseases - Yutong Zhang; Xuan Liu; Zeheng Li; Hao Li; Zhigang Miao; Bo wan; Xingshun Xu (Molecular Neurobiology, 2024)

Volcanic Hazard Mapping for Changbaishan-Tianchi Region, China - Yuan Wan; Jiandong Xu; Bo Pan; Jingwei Zhang; Hongmei Yu; Bo Zhao; Feixiang Wei (Journal of Earth Science, 2024)

Long-Circulating and Targeted Liposomes Co-loading Cisplatin and Mifamurtide: Formulation and Delivery in Osteosarcoma Cells - Bo Li; Qianhui Zhao; Hanyu Yang; Xueyuying Wang; Zhijun Zhang; Yanling Gong; Xu Wan (AAPS PharmSciTech, 2024)

Influence of surface water and groundwater gradient on spatial distribution of typical vegetation in the hinterland of Taklamakan desert - Lei Peng; Yan-Bo Wan; Hao Li; Men-Di Du; Qing-Dong Shi (Science of The Total Environment, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

Kinetic study on the effect of ice nucleation and generation on methane hydrate dissociation below the quadruple point - Ting-Ting Zhang; Bo Li; Wen-Na Wei; Jing-Chun Feng; Qing-Cui Wan (Gas Science and Engineering, 2024)

A synergetic binary system of waste cooking oil-derived bio-based surfactants and its interfacial performance for enhanced oil recovery - Ming-Yue Liang; Chi Ma; Wan-Qi Qin; Homely Isaya Mtui; Wei Wang; Jin-feng Liu; Shi-Zhong Yang; Bo-Zhong Mu (Colloids and Surfaces C: Environmental Aspects, 2024)

In situ growth of hydrophobic 3D porous Zn@Ag electrode in achieving excellent performance for eCO2RR - Shenglin Yan; Xinyu Zhang; Samah A. Mahyoub; Bo Zhang; Xiangbei Wan; Yanran Cui; Pengfei Xie; Qiong Wang; Zhenmin Cheng; Zhenglong Li (Chemical Engineering Journal, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

A novel dual-ligand copper-based nanoflower for the colorimetric and fluorescence detection of 2,4-dichlorophenol, epinephrine and hydrogen peroxide - Jia-Xin Li; Tong-Qing Chai; Guo-Ying Chen; Mao-Ling Luo; Jian-Bo Wan; Feng-Qing Yang (Analytica Chimica Acta, 2024)

An integrated strategy for in-depth profiling of N-acylethanolamines in biological samples by UHPLC-HRMS - Jun-Yi Zhou; Yan-Qing Chen; Guang Hu; Haiyu Zhao; Jian-Bo Wan (Analytica Chimica Acta, 2024)

Differential impacts of microplastics on carbon and nitrogen cycling in plant-soil systems: A meta-analysis - Yige Liu; Siyi Chen; Pengyu Zhou; Haochen Li; Quan Wan; Ying Lu; Bo Li (Science of The Total Environment, 2024)

Antibiotics suppress the expression of antimicrobial peptides and increase sensitivity of Cydia pomonella to granulosis virus - Zaiyuan Li; Lan Ouyang; Yin Lu; Qi Peng; Xi Qiao; Qiang Wu; Bin Zhang; Bo Liu; Fanghao Wan; Wanqiang Qian (Science of The Total Environment, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Combining chemical analysis and toxicological methods to access the ecological risk of complex contamination in Daye Lake - Bo Lei; Xin Wang; Ling Wang; Yue Kang; Tianying Wan; Wenjuan Li; Qingqing Yang; Jie Zhang (Science of The Total Environment, 2024)

Experimental study on human evacuation onboard passenger ships considering heeling angle and opposite directions - Siming Fang; Zhengjiang Liu; Xinjian Wang; Ben Matellini; Jin Wang; Zaili Yang; Xinyu Zhang; Bo Wan; Shengke Ni (Ocean Engineering, 2024)

A culture-dependent analysis of anaerobic methylotrophs in oil reservoir systems - Lin-Yuan Huang; Yi-Fan Liu; Wan-Qi Qin; Shi-Yi Wang; Yuan-Hao Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

The role of tissue-derived extracellular vesicles in tumor microenvironment - Jin Lin; Wan Lu; Bo Huang; Weiming Yang; Xiaozhong Wang (Tissue and Cell, 2024)

Is there Paleoproterozoic eclogite facie rock in Alxa along the northern margin of the North China Craton? - Bo Wan (Precambrian Research, 2024)

A crustal radially anisotropic shear-wave velocity model of Northwestern Australia - Tingzi Li; Liang Zhao; Rijin Zhao; Ruth E. Murdie; Klaus Gessner; Xiaobing Xu; Kun Wang; Bo Wan; Sergi Ventosa; Huaiyu Yuan (Precambrian Research, 2024)

New perspectives on enhancing waste activated sludge dewaterability through extracellular polymeric substances (EPS) biodegradation: Investigating the impact of EPS stratification and conversion - Bo Li; Ying Liu; Pengfei Wan; Xiao Yu; Heping Chen; Wenzhou Lv (Journal of Water Process Engineering, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

MOF-derived CoP/C catalyst for efficient dibenzothiophene hydrodesulfurization - Liang-Liang Zhang; Kai-Xuan Yang; Cai-Long Xue; Wan-Xi Li; Bo-Qiong Li; Yi-En Du; Yong-Qiang Chen; Ya-Jie Liu (Fuel, 2024)

Integrated framework for geological modeling: integration of data, knowledge, and methods - Hong Li; Bo Wan; Deping Chu; Run Wang; Guoxi Ma; Chuanyang Lei; Shengyong Pan (Bulletin of Engineering Geology and the Environment, 2024)

Laccaria guizhouensis sp. nov. (Agaricales, Basidiomycota) from Southwest China - San-Fang Zhang; Yang Gui; Guo-Sheng Zhu; Nian-Jie Shang; Biao Li; Tong-Jing Yang; Guang-Lu Gong; Wan-Bin Huang; Zhan-Bo Liu (New Zealand Journal of Botany, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Spatial and temporal variation of water clarity in typical reservoirs in the Beijing-Tianjin-Hebei region observed by GF1-WFV satellite data - Chang Cao; Junsheng Li; Xiaodong Jia; Shenglei Wang; Bo Wan (Journal of Oceanology and Limnology, 2024)

Deoxynivalenol and T-2 toxin cause liver damage and egg quality degradation through endoplasmic reticulum stress in summer laying hens - Haoneng. Guo; Hongyan Wan; Wenfang Lou; Rifat Ullah Khan; Jinming You; Bo Huang; Shu Hao; Guanhong Li; Sifa Dai (International Journal of Biometeorology, 2024)

Enhancing simultaneous nitrogen and phosphorus availability through biochar addition during Chinese medicinal herbal residues composting: Synergism of microbes and humus - Bo Yan; Tian Lan; Yang Lv; Chuanming Xing; Yongqi Liang; Huazhe Wang; Qinglian Wu; Liang Guo; Wan-Qian Guo (Science of The Total Environment, 2024)

A comprehensive study combing experiment and CFD simulation on the fume hood performance for nanoparticles and isopropanol control - Guan-Yu Lin; Yi-Ming Lee; Bo-Wen Chiu; Hsuan-Yu Hsu; Chuen-Wan Chen; Chuen-Jinn Tsai (Process Safety and Environmental Protection, 2024)

Contemporaneous closure of the Paleo-Asian Ocean in the Middle-Late Triassic: A synthesis of new evidence and tectonic implications for the final assembly of Pangea - Dongfang Song; Wenjiao Xiao; Songjian Ao; Qigui Mao; Bo Wan; Hao Zeng (Earth-Science Reviews, 2024)

Sulfurization-induced lattice disordering in high-entropy catalyst for promoted bifunctional electro-oxidation behavior - Jing Chen; Kexin Wang; Zimeng Liu; Xu Sun; Xiaodong Zhang; Fengcai Lei; Xiuyan Wan; Junfeng Xie; Bo Tang (Chemical Engineering Journal, 2024)

Enhanced interfacial effect via acid theory with boosted photocatalytic performance of nitenpyram removal - Ran Chen; Bo Xu; Heping Cheng; Qianqian Fang; Minghai Ma; Liping Qian; Shunli Wan; Shengyou Xu; Yan Li; Lei Zhang; Shikai Xiang (Chemosphere, 2024)

Exposure to nitrate induces intestinal inflammation, as determined by an integrated transcriptome and weighted gene co-expression network analysis in juvenile turbot (Scophthalmus maximus) - Jiachen Yu; Jie Lian; Yingying Wan; Ziyi Zhang; Jiayang Chen; Bo Qin; Pengfei Liu; Suyue Zhou; Qing Ji; Xingqiang Wang (Aquaculture, 2024)

Ultra-high electron affinity and peripheral electronegativity co-constructing all-organic dielectrics with outstanding capacitive performance at high temperature - Xiaona Li; Hang Luo; Yuting Wan; Bo Peng; Yuan Liu; Sheng Chen; Dou Zhang (Chemical Engineering Journal, 2024)

Zeolite Amendment Reduces Nitrogen and Phosphorus Leaching in Containerized Plant Production - Bo Chen; Qibing Wang; Jianjun Chen; Yuncong Li; Yongshan Wan (Water, Air, & Soil Pollution, 2024)

Interspecific occupancy-abundance relationship of benthic diatoms changes seasonally with attachment mode in a tropical river - Lin Tan; Yuting Liu; Muqi Shen; Guifeng Wei; Linglin Wan; Quehui Tang; Bo-Ping Han (Hydrobiologia, 2024)

Microplastics and cadmium affect invasion success by altering complementarity and selection effects in native community - Feng He; Jianfan Sun; Justin S.H. Wan; Mohsin Nawaz; Qaiser Javed; Linxuan Pan; Wajid Ali Khattak; Yanwen Bo; Yan Xiang; Guangqian Ren; Xin Lin; Daolin Du (Science of The Total Environment, 2024)

Exploring the effects of zeolite, biochar, and diatomite as additives for enhancing heavy metals passivation and eliminating antibiotic resistance genes in composts during vermicomposting of dewatered sludge and green waste - Xiaoqiang Gong; Wenhui Shi; Zuotao Zhang; Mengqin Luo; Bo Zhang; Shaocong Wan; Jing Huang (Journal of Environmental Chemical Engineering, 2024)

A study of guar gum derivatives as green kinetic hydrate inhibitors - Bo Liu; Xiang-Long Ding; Yi-Ming Dai; Li Wan (Journal of Environmental Chemical Engineering, 2024)

Thermodynamic design and analysis of air-liquefied energy storage combined with LNG regasification system - Qingfeng Jiang; Shiqing Wan; Chongyao Pan; Guozeng Feng; Huaibing Li; Hansheng Feng; Bo Meng; Jiayang Gu; Yunchu Feng (International Journal of Refrigeration, 2024)

Effect of initial pore water content and salinity on the resistivity of methane hydrate-bearing fine sediments - Jinan Guan; Wenchao Bo; Shujia Wang; Yian Liang; Dongliang Li; Lihua Wan; Deqing Liang (Gas Science and Engineering, 2024)

Metagenomic analysis reveals the correlations between microbial communities and flavor compounds during the brewing of traditional Fangxian huangjiu - Ruijie Gao; Pai Peng; Li Yu; Bo Wan; Xiaotong Liang; Pulin Liu; Weifang Liao; Lihong Miao (Food Bioscience, 2024)

Space-time cube uncovers spatiotemporal patterns of basin ecological quality and their relationship with water eutrophication - Zhenxiu Cao; Minghui Wu; Dezhi Wang; Bo Wan; Hao Jiang; Xiang Tan; Quanfa Zhang (Science of The Total Environment, 2024)

Deciphering the source of banded iron formations in the North China Craton - Changle Wang; Shangjun Xie; Xin Zhang; Xiaoxue Tong; Yang Bai; Zidong Peng; Zhiguo Dong; Lianchang Zhang; Bo Wan (Precambrian Research, 2024)

DIET-like and MIET-like mutualism of S. oneidensis MR-1 and metal-reducing function microflora boosts Cr(VI) reduction - Boyu Jia; Juanjuan Wan; Hui Liu; Bo Yan; Lijuan Zhang; Xintai Su (Journal of Hazardous Materials, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Erratum to: Geodynamic processes of the southeastern Neo-Tethys Ocean and the formation mechanism of the curved subduction system in Southeast Asia - Weiwei Ding; Rixiang Zhu; Bo Wan; Liang Zhao; Xiongwei Niu; Pan Zhao; Baolu Sun; Yanghui Zhao (Science China Earth Sciences, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

Carbon flux from hydrothermal skarn ore deposits and its potential impact to the environment - Wei Liu; Bo Wan (Gondwana Research, 2024)

Chemical species of Ge/W/Ga in lignite and their enrichment in thermal treatment - Jiawang Wu; Wenting Bo; Zhenyong Miao; Keji Wan (Fuel, 2024)

Multi-spherical interactions and mechanisms of hydrocarbon enrichment in the Southeast Asian archipelagic tectonic system - Rixiang Zhu; Hongjun Wang; Huajian Wang; Xiaomei Wang; Bo Wan; Wang Zhang; Houqin Zhu; Yuke Liu; Junlai Liu; Qinren Meng; Fang Hao; Zhijun Jin (Science China Earth Sciences, 2024)

Tartaric acid coupled with gibberellin improves remediation efficiency and ensures safe production of crops: A new strategy for phytoremediation - Teng-yue Yuan; Da-juan Wan; Wen-jun Yang; Jiao-feng Gu; Hang Zhou; Peng Zeng; Bo-han Liao (Science of The Total Environment, 2024)

Enhanced humus synthesis from Chinese medicine residues composting by lignocellulose-degrading bacteria stimulation: Upregulation of key enzyme activity and neglected indirect effects on humus formation - Chuan-Ming Xing; Zi-Lin He; Tian Lan; Bo Yan; Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Cai-Xia Wang; Wan-Qian Guo (Science of The Total Environment, 2024)

E. coli phage transport in porous media: Response to colloid types and water saturation - Wenjing Zhang; Shuxin Li; Kaichao Zhao; Juanfen Chai; Bo Wan; Yunqi Qin; Huan Huan; Simiao Sun; Yuesuo Yang; Muhammad Yousuf Jat Baloch (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Diverse Late Triassic arc magmatism and porphyry Cu deposits in the southeastern Tibetan Plateau: Related to slab tear along a subducting passive margin? - Wan-Li Tang; Jian-Lin Chen; Tian-Nan Yang; An Yin; Ji-Feng Xu; Jiang-Bo Ren (Lithos, 2024)

Mercury contents and isotope ratios in marine and terrestrial archives across the Cretaceous/Paleocene boundary - Sha Li; Stephen E. Grasby; Yi Xing; Edmund A. Jarzembowski; Qifei Wang; Haichun Zhang; Xiaoqiao Wan; Bo Wang (Earth-Science Reviews, 2024)

Fast ion/electron transport enabled by MXene confined bimetallic sulfides with heterostructure toward highly effective lithium/sodium storage - Yun-Lei Hou; Jing-Zhou Chen; Bo-Han Zhang; Hua-Ying Wang; Wan-Xin Wen; Dong-Lin Zhao (Chemical Engineering Journal, 2024)

Titanium isotopic fractionation during alkaline magma differentiation at St. Helena Island - Xinmiao Zhao; Xiao-Jun Wang; Xiliang Jia; Noreen J. Evans; Chunxia Yi; Li-Hui Chen; Takeshi Hanyu; Jin Li; Bo Wan; Xiangkun Zhu; Hongfu Zhang (Contributions to Mineralogy and Petrology, 2024)

Fragmentation of continental subduction is ending the Himalayan orogeny - Xiaofeng Liang; Yang Chu; Bo Wan; Ling Chen; Lin Chen; Eric Sandvol; Stephen P. Grand; Yibing Li; Minling Wang; Xiaobo Tian; Yun Chen; Tao Xu; et al. (Science Bulletin, 2023)

Ultrasonic–microwave synergistic supramolecular solvent liquid–liquid microextraction of trace biogenic amines in fish and beer based on solidification of floating organic droplet - Furong Jin; Xinyue Yin; Yang Wan; Jiukai Zhang; Jindi Wang; Xiangbo Fu; Tianxin Fu; Buwei Liu; Yongshi Chen; Bo Tian; Zhibiao Feng (Food Chemistry, 2023)

The influence of Tethyan evolution on changes of the Earth’s past environment - Bo Wan; Fuyuan Wu; Rixiang Zhu (Science China Earth Sciences, 2023)

Proteomic characteristics of six snake venoms from the Viperidae and Elapidae families in China and their relation to local tissue necrosis - Wan-Gang Qin; Zhan-Peng Zhuo; Hao Hu; Mimi Lay; Qian-Qin Li; Jun-Ting Huang; Liang-Bo Zeng; Zi-Jing Liang; Fei Long; Qing Liang (Toxicon, 2023)

Three-dimensional Meso-scale virtual strength test of steel slag porous asphalt mixture based on PFC3D - Xueqin Chen; Zhenhui Liu; Baocai Wan; Bo Yao; Qiao Dong (Journal of Cleaner Production, 2023)

Health effects of future dioxins emission mitigation from Chinese municipal solid waste incinerators - Jing Guo; Xin Bo; Yang Xie; Ling Tang; Jun Xu; Zhongzhi Zhang; Ruxing Wan; Haiyun Xu; Zhifu Mi (Journal of Environmental Management, 2023)

Cost-benefits analysis of ultra-low emissions standard on air quality and health impact in thermal power plants in China - Ruxing Wan; Ling Tang; Jing Guo; Wenhui Zhai; Ling Li; Yang Xie; Xin Bo; Jun Wu (Journal of Environmental Management, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

mitfa deficiency promotes immune vigor and potentiates antitumor effects in zebrafish - Wan-Ping Bian; Shao-Lin Xie; Chao Wang; Grigoriy G. Martinovich; Yan-Bo Ma; Pan-Pan Jia; De-Sheng Pei (Fish & Shellfish Immunology, 2023)

Quantifying the potential effects of air pollution reduction on population health and health expenditure in Taiwan - Yi-Hsuan Roger Chen; Wan-Chen Lee; Bo-Chen Liu; Po-Chieh Yang; Chi-Chang Ho; Jing-Shiang Hwang; Tzu-Hsuan Huang; Hsien-Ho Lin; Wei-Cheng Lo (Environmental Pollution, 2023)

New paleomagnetic data from the central Tethyan Himalaya refine the size of Greater India during the Campanian - Jie Yuan; Chenglong Deng; Zhenyu Yang; Wout Krijgsman; Thubtantsering; Huafeng Qin; Liang Yi; Pan Zhao; Bo Wan; Liang Zhao; Huaiyu He; Zhengtang Guo; et al. (Earth and Planetary Science Letters, 2023)

Toxic effects of combined exposure to cadmium and nitrate on intestinal morphology, immune response, and microbiota in juvenile Japanese flounder (Paralichthys olivaceus) - Pengfei Liu; Yingying Wan; Ziyi Zhang; Qing Ji; Jie Lian; Chuanzheng Yang; Xingqiang Wang; Bo Qin; Long zhu; Jiachen Yu (Aquatic Toxicology, 2023)

Contrasting platinum-group element geochemistry of post-collisional porphyry Cu ± Au ore-bearing and barren suites in the central and southeastern Urumieh-Dokhtar magmatic arc, Iran - Jiwon Hwang; Jung-Woo Park; Bo Wan; Maryam Honarmand (Mineralium Deposita, 2023)

Effects of environmental factors on the river water quality on the Tibetan Plateau: a case study of the Xoirong River, China - Minghui Wu; Bo Wan; Dezhi Wang; Zhenxiu Cao; Xiang Tan; Quanfa Zhang (Environmental Science and Pollution Research, 2023)

Integrating diverse plant bioactive ingredients with cyclodextrins to fabricate functional films for food application: a critical review - Bingren Tian; Jiayue Liu; Yumei Liu; Jian-Bo Wan (Critical Reviews in Food Science and Nutrition, 2023)

Growth of Scenedesmus obliquus on anaerobic soybean wastewater using different wasted organics for high biomass production and nutrients recycling - Xiao-Bo Tan; Zhuo-Yi Huang; Xi-Ping Wan; Zi-Jie Duan; Ya-Lei Zhang; Jian-Yu Liao (Chemosphere, 2023)

Acid-induced tubular g-C3N4 for the selective generation of singlet oxygen by energy transfer: Implications for the photocatalytic degradation of parabens in real water environments - Yu-Wei Li; Shu-Zhi Li; Min-bo Zhao; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma (Science of The Total Environment, 2023)

Dual-objective optimization of large-scale solar heating systems integrated with water-to-water heat pumps for improved techno-economic performance - Ruichao Zhang; Dengjia Wang; Zuoxiang Yu; Yongjun Sun; Hang Wan; Yanfeng Liu; Qingtai Jiao; Meng Gao; Jianhua Fan; Bo Lan (Energy and Buildings, 2023)

Designing multifunctional silica coatings for enhanced broadband antireflection and microfiber contamination sensing - Xinshu Zou; Guorui Zhou; Yi Wan; Bo Li; Bo Jiang; Hongwei Yan; Feng Wang (Chemical Engineering Journal, 2023)

TIPS: A three-dimensional phenotypic measurement system for individual maize tassel based on TreeQSM - Bo Xu; Xiangyuan Wan; Hao Yang; Haikuan Feng; Yuanyuan Fu; Haiyan Cen; Binbin Wang; Zhoufeng Zhang; Siyuan Li; Chunjiang Zhao; Guijun Yang (Computers and Electronics in Agriculture, 2023)

Plant image recognition with deep learning: A review - Ying Chen; Yiqi Huang; Zizhao Zhang; Zhen Wang; Bo Liu; Conghui Liu; Cong Huang; Shuangyu Dong; Xuejiao Pu; Fanghao Wan; Xi Qiao; Wanqiang Qian (Computers and Electronics in Agriculture, 2023)

Hydrothermal circulation at 1.8 Ga in the Kiruna area, northern Sweden, as revealed by apatite geochemical systematics - Shengchao Yan; Bo Wan; Ulf B. Andersson (Precambrian Research, 2023)

Paleostress regime evolution in South China induced by dynamic changes in Izanagi-Pacific subduction since the Cretaceous - Bo Zhang; Shaofeng Liu; Neng Wan; Qingjun Xu (Journal of Structural Geology, 2023)

Apatite age and composition: A key to the geological history of the Malmberget Iron-Oxide-Apatite (IOA) deposit and the region - Shengchao Yan; Bo Wan; Ulf B. Andersson (Journal of Geochemical Exploration, 2023)

In situ generated of hybrid interface in poly(1,3-dioxolane) quasi solid electrolyte and extended sulfone cosolvent for lithium-metal batteries - Bo-Han Zhang; Wan-Xin Wen; Hua-Ying Wang; Yun-Lei Hou; Jing-Zhou Chen; Dong-Lin Zhao (Chemical Engineering Journal, 2023)

Effect and Mechanism of Sodium Butyrate on Neuronal Recovery and Prognosis in Diabetic Stroke - Ting-ting Li; Deng-ming Zhao; Yu-ting Wei; Jing-bo Li; Xue-fei Li; Qiang Wan; Xin Zhang; Xiang-nan Liu; Wan-chao Yang; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)

Recognition of multivariate geochemical anomalies using a geologically-constrained variational autoencoder network with spectrum separable module – A case study in Shangluo District, China - Bo Zhao; Dehui Zhang; Panpan Tang; Xiaoyan Luo; Haoming Wan; Lin An (Applied Geochemistry, 2023)

Peganutonin A, a novel melatonin analogue from the seeds of Peganum harmala - Jian-Bo Liu; Wan-Ying Li; Xue Zhao; Feng-Ying Yang; Lei Fang (Phytochemistry Letters, 2023)

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Metal–support interface engineering of Ni catalysts for improved H2 storage performance: Grafting alkyltriethoxysilane onto commercial alumina - Hwi Ju Jung; Hwiram Jeong; Dongun Kim; Hyerim Ko; Gi Bo Han; Byunghun Jeong; Tae Wan Kim; Young-Woong Suh (Chemical Engineering Journal, 2023)

Role of TPEN in Amyloid-β25–35-Induced Neuronal Damage Correlating with Recovery of Intracellular Zn2+ and Intracellular Ca2+ Overloading - Wen-bo Chen; Yu-xiang Wang; Hong-gang Wang; Di An; Dan Sun; Pan Li; Tao Zhang; Wan-ge Lu; Yan-qiang Liu (Molecular Neurobiology, 2023)

From Tethyan subduction to Arabia-Eurasia continental collision: Multiple geo-thermochronological signals from granitoids in NW Iran - Zhiyong Zhang; Thomas Zack; Barry Kohn; Marco G. Malusà; Lin Wu; Mahnaz Rezaeian; Nan Wang; Dunfeng Xiang; Chao Guo; Rasoul Esmaeili; Bo Wan; Wenjiao Xiao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Soil variables and reflected light revealed the plasticity of grape and wine composition: Regulation of the flavoromics under inner row gravel covering - Meng-Bo Tian; Wan-Hui Ma; Nong-Yu Xia; Jing Peng; Rui-Qi Hu; Chang-Qing Duan; Fei He (Food Chemistry, 2023)

Development of non-isothermal wall jet integrated zonal model with enhanced accuracy using a multi-flow coefficient calibration method - Bo Lan; Hang Wan; Zhun (Jerry) Yu; Gongsheng Huang (Building and Environment, 2023)

Establishing environmental background values of selected trace elements and environmental quality assessment of fine-grained sediments in the Jiaozhou Bay catchment, China - Fangjian Xu; Xu Tian; Xianchao Wang; Xiaoming Wan; Bo Chen (Journal of Oceanology and Limnology, 2023)

Institutional capability, cooperation level and irrigation water order: Empirical analysis based on survey data from the Yellow River area - Bo Wang; Jingjing Wan; Yuchun Zhu; Yahui Chen (Irrigation and Drainage, 2023)
Village rules and customs, reciprocal trust and favour and mobilization ability are the main factors affecting governance ability in rural public affairs. Based on microsurvey data from 979 irrigating farmers from the Yellow River area in China, the effects of three types of village institutional capacity factors (knowledge resources, relational resources and mobilization capacity) on the irrigation behaviour and the irrigation water order of village farmland were analysed. The results indicate that these factors would reduce villagers' water‐stealing behaviour and water‐use disputes during the irrigation process, strengthen water‐use satisfaction of the villagers and ultimately improve the order of farmland‐irrigation water in the whole village. The level of cooperation within irrigation organizations has a moderating effect on this process, and higher levels of cooperation lead to a greater positive impact of these institutional capacity factors on villagers' water‐use behaviour.

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

A thermodynamic model of integrated liquid-to-liquid thermoelectric heat pump systems - Hanlong Wan; Kyle R. Gluesenkamp; Bo Shen; Zhenning Li; Viral K. Patel; Navin Kumar (International Journal of Refrigeration, 2023)

Characteristics of unloading damage and permeability evolution of sandstone under hydro-mechanical coupling - Rubin Wang; Bo Xu; Yu Wan; Huanling Wang; Wei Wang; Qingxiang Meng (European Journal of Environmental and Civil Engineering, 2023)

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

First report of cowpea mild mottle virus infecting adzuki bean in China - Shuhao Lu; Xulong Wang; Bo Zhao; Jianping Yu; Yongjiang Zhang; Yongqiang Li; Ping Wan (Journal of Plant Pathology, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

PRRSV infection activates NLRP3 inflammasome through inducing cytosolic mitochondrial DNA stress - Huawei Li; Xiaotian Yang; Yuzhen Song; Qingguo Zhu; Ziqian Liao; Yixuan Liang; Jianghao Guo; Bo Wan; Dengke Bao (Veterinary Microbiology, 2023)

Geodynamic processes of the southeastern Neo-Tethys Ocean and the formation mechanism of the curved subduction system in Southeast Asia - Weiwei Ding; Rixiang Zhu; Bo Wan; Liang Zhao; Xiongwei Niu; Pan Zhao; Baolu Sun; Yanghui Zhao (Science China Earth Sciences, 2023)

An integrated method to identify and evaluate the impact of hydropower development on terrestrial ecosystem - Hang Wan; Yulei Xie; Bo Li; Yanpeng Cai; Zhifeng Yang (Environmental Impact Assessment Review, 2023)

Trim28 citrullination maintains mouse embryonic stem cell pluripotency via regulating Nanog and Klf4 transcription - Yaguang Zhang; Xiaowen Wan; Lei Qiu; Lian Zhou; Qing Huang; Mingtian Wei; Xueqin Liu; Sicheng Liu; Bo Zhang; Junhong Han (Science China Life Sciences, 2023)

Identification of a novel cyclomaltodextrinase annotated as a neopullulanase in the genome of Bacillus cereus - Bo-Ram Park; Davoodbasha MubarakAli; Jung-Wan Kim (Archives of Microbiology, 2023)

Microplastics reduce nitrogen uptake in peanut plants by damaging root cells and impairing soil nitrogen cycling - Yiyang Liu; Fangji Xu; Liping Ding; Guanchu Zhang; Bo Bai; Yan Han; Lina Xiao; Yan Song; Ying Li; Shubo Wan; Guowei Li (Journal of Hazardous Materials, 2023)

Air pollutant emissions and reduction potentials from municipal solid waste incineration in China - Ling Tang; Jing Guo; Ruxing Wan; Min Jia; Jiabao Qu; Ling Li; Xin Bo (Environmental Pollution, 2023)

Changes in aquaporins expression due to acute water restriction in naturally aging mice - So-Jeong Kim; Kyung-Wan Baek; Youn-Kwan Jung; Ji-Seok Kim; Bo-Gyu Kim; Hak Sun Yu; Jin Sung Park; Jun-Il Yoo (Journal of Physiology and Biochemistry, 2023)

Characteristics of debris flow impact on a double-row slit dam - Zhuang Wang; Dao-chuan Liu; Yong You; Xiao-bo Lyu; Jin-feng Liu; Wan-yu Zhao; Hao Sun; Dong-wei Wang; Yang Liu (Journal of Mountain Science, 2023)

Development of Electromagnetic Current Meter for Marine Environment - Shizhe Chen; Yushang Wu; Shixuan Liu; Yingdong Yang; Xiaozheng Wan; Xianglong Yang; Keke Zhang; Bo Wang; Xingkui Yan (Journal of Marine Science and Engineering, 2023)
Ocean current is one of the most important parameters in ocean observation, and ocean current measurement based on electromagnetic induction is becoming more and more important because of its advantages such as simple structure and high measurement accuracy. However, it is difficult to detect weak current signals in a complex marine environment. In this paper, an electromagnetic induction current measurement scheme based on lock-in amplification technology is proposed. Key technologies such as the evaluation of induced current intensity, overall design, circuit design, and orientation design of the current meter were studied. The prototype of the electromagnetic current meter was developed and tested in the laboratory and at sea. The repeatability of current velocity and current direction was higher than 1.5 cm/s and 1.5°, respectively. A comparison test between the electromagnetic current meter prototype and Nortek ADCP (Acoustic Doppler Current Profiler) installed on a buoy at sea was carried out, and the correlation coefficients of the current velocity and current direction datum were 0.90 and 0.96, respectively. Through continuous on-site and fault-free operations at sea, the experimental data show that the electromagnetic current meter has good adaptability at sea, which provides feasible technical and equipment support for ocean current observation.

Recovery of polyhydroxyalkanoates (PHAs) polymers from a mixed microbial culture through combined ultrasonic disruption and alkaline digestion - Yuqi Zou; Mingfeng Yang; Qiuyue Tao; Keliang Zhu; Xiang Liu; Chunli Wan; Marie K. Harder; Qun Yan; Bo Liang; Ioanna Ntaikou; Georgia Antonopoulou; Gerasimos Lyberatos; et al. (Journal of Environmental Management, 2023)

Design and efficacy of all-in-one sandwich-like multifunctional platform for drug delivery - Bo Zhang; Yumei Qin; Yanyan Li; Yu Wang; Huining Wan; Xiyu Liu; Xiaoqin Hu; Yongqi An; Hao Zhang; Li Yang; Rifang Luo; Yunbing Wang (Chemical Engineering Journal, 2023)

High-resolution mapping and driving factors of soil erodibility in southeastern Tibet - Wu Yu; Yefeng Jiang; Wandong Liang; Dan Wan; Bo Liang; Zhou Shi (CATENA, 2023)

Characteristics of gully bed scour and siltation between check dams - Xiao-bo Lyu; Yong You; Zhuang Wang; Jin-feng Liu; Hao Sun; Wan-yu Zhao (Journal of Mountain Science, 2023)

Effect of polyaspartic acid on soil water storage, soil microbial diversity, cotton yield and fiber quality - Wen-long Liu; Jian-Bo Zhao; Hong Zeng; Chuan-xing Wan (Archives of Microbiology, 2023)

Hyperparameter Optimization for the LSTM Method of AUV Model Identification Based on Q-Learning - Dianrui Wang; Junhe Wan; Yue Shen; Ping Qin; Bo He (Journal of Marine Science and Engineering, 2022)
An accurate mathematical model is a basis for controlling and estimating the state of an Autonomous underwater vehicle (AUV) system, so how to improve its accuracy is a fundamental problem in the field of automatic control. However, AUV systems are complex, uncertain, and highly non-linear, and it is not easy to obtain through traditional modeling methods. We fit an accurate dynamic AUV model in this study using the long short-term memory (LSTM) neural network approach. As hyper-parameter values have a significant impact on LSTM performance, it is important to select the optimal combination of hyper-parameters. The present research uses the improved Q-learning reinforcement learning algorithm to achieve this aim by improving its recognition accuracy on the verification dataset. To improve the efficiency of action exploration, we improve the Q-learning algorithm and choose the optimal initial state according to the Q table in each round of learning. It can effectively avoid the ineffective exploration of the reinforcement learning agent between the poor-performing hyperparameter combinations. Finally, the experiments based on simulated or actual trial data demonstrate that the proposed model identification method can effectively predict kinematic motion data, and more importantly, the modified Q-Learning approach can optimize the network hyperparameters in the LSTM.

Amphibolites from makran accretionary complex record Permian-Triassic Neo-Tethyan evolution - Rasoul Esmaeili; Songjian Ao; Hadi Shafaii Moghadam; Zhiyong Zhang; William L. Griffin; Mohammad Ebrahimi; Wenjiao Xiao; Bo Wan; Saunak Bhandari (International Geology Review, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Whole Genome Sequencing and Biological Characteristics of Two Strains of Porcine Escherichia coli Isolated from Saba Pigs - Bo Zhang; Weiwei Zhao; Bin Gao; Chunlan Shan; Xi Wang; Quan Wan; Jing Deng; Jinglong Cha; Bingxun Chen; Dongmei Han; Libo Gao; Pingxing Ao; et al. (Current Microbiology, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Amicoumacins from a desert bacterium: quorum sensing inhibitor against Chromobacterium violaceum - Wen-Pan Shi; Hong Zeng; Chuan-Xing Wan; Zhong-Bo Zhou (Natural Product Research, 2021)

Impact of Freshwater Discharge on the Carbon Uptake Rate of Phytoplankton During Summer (January–February 2019) in Marian Cove, King George Island, Antarctica - Bo Kyung Kim; Misa Jeon; Hyoung Min Joo; Tae-Wan Kim; Sang-Jong Park; Jisoo Park; Sun-Yong Ha (Frontiers in Marine Science, 2021)
Rapidly changing conditions in high-latitude coastal systems can significantly impact biogeochemical cycles because these systems are strongly influenced by freshwater discharged from melting glaciers and streams on land. Generally, Antarctic coastal areas are considered high-productivity areas in which phytoplankton growth prevails under various environmental conditions (e.g., oceanographic and meteorological conditions). This study provides carbon uptake rates of phytoplankton in Marian Cove during summer (January-February 2019). Daily depth-integrated carbon uptake varied greatly and averaged 0.8 g C m –2 day –1 , with a maximum of 4.52 mg g C m –2 day –1 recorded on 14 January. Similarly, the observed biomass standing stocks were very high (up to 19.5 mg m –3 chlorophyll a ) and were dominated by microphytoplankton (20–200 μm), representing 84% of total chlorophyll a (chl- a ). The depth-integrated chl- a and carbon uptake decreased from outer to inner areas (close to the glacial front) in the cove. As the austral summer progressed, the freshening of the surface waters coincided with high water stability and suspended material and with low productivity when nanophytoplankton were present (2–20 μm; >60%). These findings suggest that both photosynthetically active radiation penetrating the water column and enhanced turbidity control light availability for phytoplankton, as well as their community compositions.

Exposure to phthalates and cardiovascular diseases in Chinese with type 2 diabetes - Haojie Zhang; Jingsi Chen; Chi Chen; Heng Wan; Yi Chen; Yuying Wang; Wen Zhang; Bo Chen; Ningjian Wang; Yingli Lu (Environmental Science and Pollution Research, 2021)

Triglyceride regulate ACE2 level through MTHFD1 - Xiaohua Ma; Xiaojing Li; Bo Wan; Zhigang Miao (Journal of Biosciences, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Spatiotemporal characteristics and trend assessment of Ms ≥ 5.6 earthquakes in the Tianshan area of China based on co-occurrence analysis and commensurability - Jia Wan; Jun-Ping Yan; Zi-Qiang Liu; Xiao-Meng Wang; Yu-Feng Zhang; Cheng-Bo Wang (Applied Geophysics, 2021)

Increased susceptibility to temperature variation for non-accidental emergency ambulance dispatches in Shenzhen, China - Wenjing Wu; Bo Chen; Gonghua Wu; Yunying Wan; Qiang Zhou; Hua Zhang; Juying Zhang (Environmental Science and Pollution Research, 2021)

Devonian arc-related granitoids in the Northwestern Chinese Tianshan, Central Asian Orogenic Belt: implications for the bending of the Kazakhstan Orocline - Minjia Sun; Keda Cai; Min Sun; Bo Wan; Xiangsong Wang; Zihe Bao (International Geology Review, 2021)

A new chlorine-containing iridoid glycoside from Plantago maxima - Liang-Liang Ma; Lu-Lu Wang; Yue-Feng Zhang; Xiang-Fu Jiang; Xin-Liu Zhu; Ke Pan; Chuan-Xing Wan; Zhong-Bo Zhou (Natural Product Research, 2021)

miR-34c inhibits PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway - Wei-feng Wan; Xin Zhang; Chang-ren Huang; Li-gang Chen; Xiao-bo Yang; Kun-yang Bao; Tang-ming Peng (Molecular Biology Reports, 2021)
The purpose of this study was to explore the effect of miR-34c on PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway, so as to find a new method for early diagnosis and treatment of cardiovascular disease. HA-VSMCs were treated with platelet-derived growth factor-BB (PDGF-BB) at 0 h, 12 h, 24 h, 48 h or 36 h to explore the optimal time for phenotypic transformation of VSMCs. And then, PDGF-BB-induced HA-VSMCs were transfected with miR-34c mimics/mimics NC and pcDNA3.1-PDGFR-β/pcDNA3.1-NC to observe cell biological behaviour. CCK8 was used to detect cell proliferation activity. Transwell chamber assay was used to detect cell invasion. Early apoptosis was analyzed by flow cytometry. The expression of α-SMA and Smemb was detected by immunofluorescence staining. The expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 were analyzed by Western blot analysis. The expression of miR-34a, miR-34b and miR-34c was detected by RT-PCR, and the targeting relationship between miR-34c and PDGFR-β was detected by luciferase reporting assay. The results indicated the proliferation and migration of PDGF-BB-induced HA-VSMCs significantly increased, and apoptosis significantly decreased. Besides, α-SMA decreased significantly, while Smemb increased significantly. Furthermore, expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 increased significantly, and SIRT1 decreased significantly. Experimental results showed that, miR-34c mimics significantly inhibited cell proliferation and migration, and promoted cell apoptosis, and miR-34c inhibitor had the opposite effects. MiR-34c mimics significantly increased α-SMA expression and decreased Smemb expression, while the opposite effects were reflected after transfection with miR-34c inhibitor. Moreover, miR-34c mimics significantly decreased the expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1, and significantly increased the expression of SIRT1, while miR-34c inhibitor had the opposite effects. Luciferase assay confirmed that PDGFR-β was a potential target of miR-34c. Subsequently, PDGF-BB-induced HA-VSMCs were co-transfected with miR-34c mimics and pcDNA3.1-PDGFR-β. The results indicated that PDGFR-β reversed the biological function of miR-34c mimic. The results revealed the potential application value of miR-34c as a marker molecule of phenotypic transformation, providing a potential target for improving phenotypic transformation.

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

The youngest matrix of 234 Ma of the Kanguer accretionary mélange containing blocks of N-MORB basalts: constraints on the northward subduction of the Paleo-Asian Kanguer Ocean in the Eastern Tianshan of the Southern Altaids - Songjian Ao; Qigui Mao; Brian F. Windley; Dongfang Song; Zhiyong Zhang; Ji’en Zhang; Bo Wan; Chunming Han; Wenjiao Xiao (International Journal of Earth Sciences, 2021)

The effect of aging on VEGF/VEGFR2 signal pathway genes expression in rat liver sinusoidal endothelial cell - Wan-Li Wang; Xing-Long Zheng; Qing-Shan Li; Wen-Yan Liu; Liang-Shuo Hu; Huan-Chen Sha; Kun Guo; Yi Lv; Bo Wang (Molecular and Cellular Biochemistry, 2021)

Injectable Hydrogel Containing Tauroursodeoxycholic Acid for Anti-neuroinflammatory Therapy After Spinal Cord Injury in Rats - Gong Ho Han; Seong Jun Kim; Wan-Kyu Ko; Daye Lee; Jae Seo Lee; Haram Nah; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2020)

Colonization on Cotton Plants with a GFP Labeled Strain of Bacillus axarquiensis - Bo Wang; Chuan-xing Wan; Hong Zeng (Current Microbiology, 2020)

Makran ophiolitic basalts (SE Iran) record Late Cretaceous Neotethys plume-ridge interaction - Rasoul Esmaeili; Wenjiao Xiao; Mohammad Ebrahimi; Ji’En Zhang; Zhiyong Zhang; Yasser Abd El-Rahman; Chunming Han; Bo Wan; Songjian Ao; Dongfang Song; Shirin Shahabi; Arthur Aouizerat (International Geology Review, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Assessment with remotely sensed soil moisture products and ground-based observations over three dense network - Gang Yang; Peng Guo; Xican Li; Hong Wan; Chunhong Meng; Bo Wang (Earth Science Informatics, 2020)

Correction to: Inhibitor of growth 2 regulates the high glucose-induced cell cycle arrest and epithelial-to-mesenchymal transition in renal proximal tubular cells - Yuan Ma; Ruijuan Yan; Qiang Wan; Bo Lv; Ying Yang; Tingting Lv; Wei Xin (Journal of Physiology and Biochemistry, 2020)

Inhibitor of growth 2 regulates the high glucose-induced cell cycle arrest and epithelial-to-mesenchymal transition in renal proximal tubular cells - Yuan Ma; Ruijuan Yan; Qiang Wan; Bo Lv; Ying Yang; Tingting Lv; Wei Xin (Journal of Physiology and Biochemistry, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Identification and Validation of Reference Genes in the Adzuki Bean (Vigna angularis) Under Iron Deficiency Using Quantitative Real-Time PCR - Junshuai Wang; Kai Yang; Bo Zhao; Yisong Li; Ping Wan (Plant Molecular Biology Reporter, 2020)

MPTP-Induced Impairment of Cardiovascular Function - Xiaoli Liu; Bo Wei; Qianqian Bi; Qihang Sun; Li Li; Jian He; Yuancheng Weng; Shenyan Zhang; Genxiang Mao; Yizhong Bao; Shu Wan; Xiao Z. Shen; et al. (Neurotoxicity Research, 2020)

Correction to: Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2020)

Accretionary processes and metallogenesis of the Central Asian Orogenic Belt: Advances and perspectives - Wenjiao Xiao; Dongfang Song; Brian F. Windley; Jiliang Li; Chunming Han; Bo Wan; Ji’en Zhang; Songjian Ao; Zhiyong Zhang (Science China Earth Sciences, 2020)

Subduction tectonics vs. Plume tectonics—Discussion on driving forces for plate motion - Ling Chen; Xu Wang; Xiaofeng Liang; Bo Wan; Lijun Liu (Science China Earth Sciences, 2020)

Flavonoids from Rhynchosia minima root exerts anti-inflammatory activity in lipopolysaccharide-stimulated RAW 264.7 cells via MAPK/NF-κB signaling pathway - Xuejing Jia; Chao Zhang; Jiaolin Bao; Kai Wang; Yanbei Tu; Jian-Bo Wan; Chengwei He (Inflammopharmacology, 2020)

Cyclical one-way continental rupture-drift in the Tethyan evolution: Subduction-driven plate tectonics - Bo Wan; Fuyuan Wu; Ling Chen; Liang Zhao; Xiaofeng Liang; Wenjiao Xiao; Rixiang Zhu (Science China Earth Sciences, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Transcriptome-wide analysis to dissect the transcription factors orchestrating the phase change from vegetative to reproductive development in Larix kaempferi - Wei-Bo Xiang; Wan-Feng Li; Shou-Gong Zhang; Li-Wang Qi (Tree Genetics & Genomes, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

n-3 Polyunsaturated fatty acids for the management of alcoholic liver disease: A critical review - Meng Wang; Li-Juan Ma; Yan Yang; Zeyu Xiao; Jian-Bo Wan (Critical Reviews in Food Science and Nutrition, 2019)

The Influence of Large Scale Phosphate Mining on the Water Quality of the Huangbaihe River Basin in China: Dominant Pollutants and Spatial Distributions - Gebrehiwet Legese Reta; Xiaohua Dong; Bob Su; Xiaonong Hu; Huijuan Bo; Hao Wan; Ji Liu; Yinghai Li; Tao Peng; Haibo Ma; Kai Wang; Shijin Xu (Mine Water and the Environment, 2019)

Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2019)

Ursodeoxycholic Acid Inhibits Inflammatory Responses and Promotes Functional Recovery After Spinal Cord Injury in Rats - Wan-Kyu Ko; Seong Jun Kim; Min-Jae Jo; Hyemin Choi; Donghyun Lee; Il Keun Kwon; Soo-Hong Lee; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2019)

Identification Standard for ENSO Events and Its Application to Climate Monitoring and Prediction in China - Hong-Li Ren; Bo Lu; Jianghua Wan; Ben Tian; Peiqun Zhang (Journal of Meteorological Research, 2018)

Fungal elicitors stimulate biomass and active ingredients accumulation in Dendrobium catenatum plantlets - Bo Zhu; Lingshang Wu; Haitong Wan; Ke Yang; Jinping Si; Luping Qin (Biologia, 2018)

The genesis of Mo-Cu deposits and mafic igneous rocks in the Senj area, Alborz magmatic belt, Iran - Ghasem Nabatian; Xian-Hua Li; Bo Wan; Maryam Honarmand (Mineralogy and Petrology, 2018)

An extreme negative Indian Ocean Dipole event in 2016: dynamics and predictability - Bo Lu; Hong-Li Ren; Adam A. Scaife; Jie Wu; Nick Dunstone; Doug Smith; Jianghua Wan; Rosie Eade; Craig MacLachlan; Margaret Gordon (Climate Dynamics, 2018)

Female Hormone 17β-Estradiol Downregulated MMP-2 Expression and Upregulated A1PI Expression in Human Corneal Stromal Cells - Hongbo Yin; Qi Wan; Yan Tian; Bo Zhao; Yingping Deng (Cell Biochemistry and Biophysics, 2018)

PKM2 knockdown influences SREBP activation and lipid synthesis in bovine mammary-gland epithelial MAC-T cells - Bing-Qian Su; Ying-Qian Han; Shuang-Shuang Fan; Sheng-Li Ming; Bo Wan; Wei-Fei Lu; Bei-Bei Chu; Guo-Yu Yang; Jiang Wang (Biotechnology Letters, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

ATP7B Mutation Detection and Pathogenicity Analysis: One Atypical Case of Wilson’s Disease with Adrenocortical Insufficiency - Min Liu; Meifang Jin; Xuqin Chen; Bo Wan; Yue Guo; Mao Sheng; Linqi Chen; Lei Zhao; Danping Huang; Yan Li (Journal of Molecular Neuroscience, 2018)

Serum Copeptin Predicts Severity and Recurrent Stroke in Ischemic Stroke Patients - Wan-Zhong Tang; Xiao-Bo Wang; Huan-Ting Li; Mei Dong; Xiang Ji (Neurotoxicity Research, 2017)

Examination of chloritization of biotite as a tool for reconstructing the physicochemical parameters of mineralization and associated alteration in the Zafarghand porphyry copper system, Ardestan, Central Iran: mineral-chemistry and stable isotope analyses - Maryam Aminroayaei Yamini; Faramarz Tutti; Mohammad Reza Aminoroayaei Yamini; Jamshid Ahmadian; Bo Wan (Mineralogy and Petrology, 2017)

Failure Mechanisms and Evolution Assessment of the Excavation Damaged Zones in a Large-Scale and Deeply Buried Underground Powerhouse - Hai-bo Li; Ming-chang Liu; Wan-bo Xing; Shuai Shao; Jia-wen Zhou (Rock Mechanics and Rock Engineering, 2017)

Enriched Endogenous Omega-3 Fatty Acids in Mice Ameliorate Parenchymal Cell Death After Traumatic Brain Injury - Huixia Ren; Zhen Yang; Chuanming Luo; Haitao Zeng; Peng Li; Jing X Kang; Jian-Bo Wan; Chengwei He; Huanxing Su (Molecular Neurobiology, 2017)

Global ionospheric electron density estimation based on multisource TEC data assimilation - Chengli She; Weixing Wan; Xinan Yue; Bo Xiong; You Yu; Feng Ding; Biqiang Zhao (GPS Solutions, 2017)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Detrital zircon provenance analysis in the Zagros Orogen, SW Iran: implications for the amalgamation history of the Neo-Tethys - Zhiyong Zhang; Wenjiao Xiao; Mahmoud Reza Majidifard; Rixiang Zhu; Bo Wan; Songjian Ao; Ling Chen; Mahnaz Rezaeian; Rasoul Esmaeili (International Journal of Earth Sciences, 2017)

The K+/H+ antiporter AhNHX1 improved tobacco tolerance to NaCl stress by enhancing K+ retention - Wei-Wei Zhang; Jing-Jing Meng; Jin-Yi Xing; Sha Yang; Feng Guo; Xin-Guo Li; Shu-Bo Wan (Journal of Plant Biology, 2017)

Life history and life table of the host-feeding parasitoid Hemiptarsenus varicornis (Hymenoptera: Eulophidae) - Xiao-Qin Cheng; Feng-Qin Cao; Yi-Bo Zhang; Jian-Yang Guo; Fang-Hao Wan; Wan-Xue Liu (Applied Entomology and Zoology, 2017)

Dimeric furanocoumarins from the roots of Angelica dahurica - Wan-Qing Yang; Zhi-Xiang Zhu; Yue-Lin Song; Bo-Wen Qi; Juan Wang; Cong Su; Peng-Fei Tu; She-Po Shi (Natural Product Research, 2017)

An Experimental Investigation into the Effects of the Anisotropy of Shale on Hydraulic Fracture Propagation - Chong Lin; Jianming He; Xiao Li; Xiaole Wan; Bo Zheng (Rock Mechanics and Rock Engineering, 2017)

Cell suspension culture of Orostachys cartilaginous in bioreactor systems for bioactive compound production and evaluation of their antioxidant properties - Xuan-Chun Piao; Wan-Bo Zhang; Jun Jiang; Ying-Hua Jin; Pyo-Jam Park; Seong-Eun Kim; Mei-Lan Lian (Acta Physiologiae Plantarum, 2017)

Prediction of primary climate variability modes at the Beijing Climate Center - Hong-Li Ren; Fei-Fei Jin; Lianchun Song; Bo Lu; Ben Tian; Jinqing Zuo; Ying Liu; Jie Wu; Chongbo Zhao; Yu Nie; Peiqun Zhang; Jin Ba; et al. (Journal of Meteorological Research, 2017)

Optimized culture medium for the production of flavonoids from Orostachys cartilaginea V.N. Boriss. callus cultures - Wan Bo Zhang; Xuan Chun Piao; Jin Rong Li; Ying Hua Jin; Mei Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2017)

Exploring the possible binding mode of trisubstituted benzimidazoles analogues in silico for novel drug designtargeting Mtb FtsZ - Ding Li; Bo Chi; Wei-Wei Wang; Jin-Ming Gao; Jian Wan (Medicinal Chemistry Research, 2017)

Enriched Endogenous Omega-3 Polyunsaturated Fatty Acids Protect Cortical Neurons from Experimental Ischemic Injury - Zhe Shi; Huixia Ren; Chuanming Luo; Xiaoli Yao; Peng Li; Chengwei He; Jing-X Kang; Jian-Bo Wan; Ti-Fei Yuan; Huanxing Su (Molecular Neurobiology, 2016)

A tomato plastidic ATP/ADP transporter gene SlAATP increases starch content in transgenic Arabidopsis - Feibing Wang; Yuxiu Ye; Yuan Niu; Faxiang Wan; Bo Qi; Xinhong Chen; Qing Zhou; Boqing Chen (Physiology and Molecular Biology of Plants, 2016)

Evaluation and quantitative analysis of different growth periods of herb–arbor intercropping systems using HPLC and UV–vis methods coupled with chemometrics - Bo-wen Chu; Ji Zhang; Zhi-min Li; Yan-li Zhao; Zhi-tian Zuo; Yuan-zhong Wang; Wan-yi Li (Journal of Natural Medicines, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

Satellite evidence for no change in terrestrial latent heat flux in the Three-River Headwaters region of China over the past three decades - YUNJUN YAO; SHAOHUA ZHAO; HUAWEI WAN; YUHU ZHANG; BO JIANG; KUN JIA; MENG LIU; JINHUI WU (Journal of Earth System Science, 2016)

Endogenous Docosahexaenoic Acid (DHA) Prevents Aβ1–42 Oligomer-Induced Neuronal Injury - Yuan Tan; Huixia Ren; Zhe Shi; Xiaoli Yao; Chengwei He; Jing-X Kang; Jian-Bo Wan; Peng Li; Ti-Fei Yuan; Huanxing Su (Molecular Neurobiology, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Source appointment of fine particle number and volume concentration during severe haze pollution in Beijing in January 2013 - Zirui Liu; Yuesi Wang; Bo Hu; Dongsheng Ji; Junke Zhang; Fangkun Wu; Xin Wan; Yonghong Wang (Environmental Science and Pollution Research, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

The application study on the multi-scales integrated prediction method to fractured reservoir description - Shuang-Quan Chen; Lian-Bo Zeng; Ping Huang; Shao-Han Sun; Wan-Lu Zhang; Xiang-Yang Li (Applied Geophysics, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Changes in digestive enzyme activities during larval development of Chinese loach Paramisgurnus dabryanus (Dabry de Thiersant, 1872) - Yun-Long Zhang; Qiao-Wan Wu; Wei-Hua Hu; Fan Wang; Zhong-Bo Zhao; Hui He; Wei-Han Shao; Qi-Xue Fan (Fish Physiology and Biochemistry, 2015)

Research on Acute Toxicity and Pharmacodynamics of Jinyulian Oral Solution - Wan-Qing Cheng; Zhen-Jian Zhang; Chuan-Bin Cao; Xiao-Wen Ye; Wang-Ping Pan; Si-Ying Ye; Bo Zhu (Cell Biochemistry and Biophysics, 2015)
A research on Jinyulian Oral Solution was conducted and the objectives were to discover its possible acute toxicity and antibacterial effects when used in vitro and in vivo. Regarding the acute toxicity test, Kunming mice were fed a maximum amount of the solution as their stomachs could hold, i.e., 40 mL kg −1 . To ascertain the minimum inhibitory concentration (MIC) of the solution, two types of germs, i.e., Staphylococcus aureus and Escherichia coli , were selected and tube dilution method was adopted. An antibacterial experimental model relying on animals’ body was developed for the researchers to observe the solution’s antibacterial effects. Test results showed that no abnormalities were discovered within 14 days after the initial date of testing and the mice grew as normal when fed with an amount of the solution 250 times of a normal clinical doze (In this case a man was assumed to weigh 60 kg.) and that the solution demonstrated obvious antibacterial effects on the two types of selected germs. The respective measured MIC 50 and MIC 90 values of the two germs were 3.2, 12.8, 6.4, and 25.6 mg L −1 . Therefore, it is reasonable to conclude that Jinyulian Oral Solution possesses no acute toxicity but obvious antibacterial effects on the two before-mentioned germs.

Study on the Structure of Candida Albicans–Staphylococcus Epidermidis Mixed Species Biofilm on Polyvinyl Chloride Biomaterial - Ying Chen; Xiao-yan Wang; Yun-chao Huang; Guang-qiang Zhao; Yu-jie Lei; Lian-hua Ye; Qiu-bo Huang; Wan-shi Duan (Cell Biochemistry and Biophysics, 2015)

Peanut violaxanthin de-epoxidase alleviates the sensitivity of PSII photoinhibition to heat and high irradiance stress in transgenic tobacco - Sha Yang; De-Yun Meng; Lin-Lin Hou; Yan Li; Feng Guo; Jing-Jing Meng; Shu-Bo Wan; Xin-Guo Li (Plant Cell Reports, 2015)

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Host instar suitability in two invasive whiteflies for the naturally occurring parasitoid Eretmocerus hayati in China - Yi-Bo Zhang; Nian-Wan Yang; Li-Ying Sun; Fang-Hao Wan (Journal of Pest Science, 2015)

What are the effects of aromatic plants and meteorological factors on Pseudococcus comstocki and its predators in pear orchards? - Hui Hua Wan; Bei Zhou Song; Guang Bo Tang; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2015)

Effects of wave action and grazers on frond perforation of the green alga, Ulva australis - Han Gil Choi; Bo Yeon Kim; Seo Kyoung Park; Jin Suk Heo; Changsong Kim; Young Sik Kim; Ki Wan Nam (Algae, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

Experimental Study on the Effect of Electrostimulation on Neural Regeneration After Oculomotor Nerve Injury - Ningxi Zhu; Chunmei Zhang; Zhen Li; Youqiang Meng; Baohui Feng; Xuhui Wang; Min Yang; Liang Wan; Bo Ning; Shiting Li (Journal of Molecular Neuroscience, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

Tectonic implications of Re-Os dating of molybdenum deposits in the Tianshan–Xingmeng Orogenic Belt, Central Asia - Chunming Han; Wenjiao Xiao; Guochun Zhao; Benxun Su; Songjian Ao; Jien Zhang; Zhiyong Zhang; Bo Wan; Zhongmei wang (International Geology Review, 2014)

BRSK2 is a valosin-containing protein (VCP)-interacting protein that affects VCP functioning in endoplasmic reticulum-associated degradation - Yingli Wang; Bo Wan; Jun Zhou; Ruwei Li; Long Yu (Biotechnology Letters, 2013)

Isolation, Identification and Characterization of Lactic Acid Bacteria From Shao-jiou-luo (Fermented Zoned Cerith), a Traditional Fermented Food in Taiwan - Yi-Sheng Chen; Hui-Chung Wu; Huei-Yin Lo; Wen-Hsuan Hsu; Wan-Chen Lin; Bo-Ya Lin (Journal of Aquatic Food Product Technology, 2013)

Oculomotor Nerve Injury Induces Nuerogenesis in the Oculomotor and Edinger–Westphal Nucleus of Adult Dog - Ningxi Zhu; Chunmei Zhang; Zhen Li; Youqiang Meng; Baohui Feng; Xuhui Wang; Min Yang; Liang Wan; Bo Ning; Shiting Li (Journal of Molecular Neuroscience, 2013)

Endoplasmic reticulum stress leads to lipid accumulation through upregulation of SREBP-1c in normal hepatic and hepatoma cells - Dian-liang Fang; Ying Wan; Wei Shen; Jie Cao; Zhong-xin Sun; Hui-hong Yu; Qin Zhang; Wen-hui Cheng; Juan Chen; Bo Ning (Molecular and Cellular Biochemistry, 2013)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

Marker-assisted selection of Verticillium wilt resistance in progeny populations of upland cotton derived from mass selection-mass crossing - Cheng-Qi Li; Guan-Shen Liu; Hai-Hong Zhao; Li-Juan Wang; Xiao-Fei Zhang; Ying Liu; Wan-Yang Zhou; Liu-Liu Yang; Peng-Bo Li; Qing-Lian Wang (Euphytica, 2013)

Land surface emissivity retrieval from satellite data - Zhao-Liang Li; Hua Wu; Ning Wang; Shi Qiu; José A. Sobrino; Zhengming Wan; Bo-Hui Tang; Guangjian Yan (International Journal of Remote Sensing, 2013)

Palaeozoic porphyry Cu–Au and ultramafic Cu–Ni deposits in the eastern Tianshan orogenic belt: temporal constraints from U–Pb geochronology - Zhongkun Han; Chunming Han; Wenjiao Xiao; Guochun Zhao; Zhongmei Wang; Songjian Ao; Jien Zhang; Bo Wan (International Geology Review, 2013)

Repellent and attractive effects of herbs on insects in pear orchards intercropped with aromatic plants - Guang Bo Tang; Bei Zhou Song; Ling Ling Zhao; Xu Sheng Sang; Hui Hua Wan; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2013)

Define the energy cone threshold and extent of Tianchi volcano - Yuan Wan; Jiandong Xu; Bo Pan (Journal of Earth Science, 2012)

Morphological and biochemical differences in three Undaria pinnatifida populations in Korea - Kwang-Jae Park; Bo-Yeon Kim; Seo-Kyoung Park; Jong-Hwa Lee; Young-Sik Kim; Han-Gil Choi; Ki-Wan Nam (Algae, 2012)

Calmodulin-binding protein CBP60g is a positive regulator of both disease resistance and drought tolerance in Arabidopsis - Dongli Wan; Ruili Li; Bo Zou; Xin Zhang; Jingyu Cong; Ruigang Wang; Yiji Xia; Guojing Li (Plant Cell Reports, 2012)

Construction of a human scFv antibody library with VH regions randomized and its application - Yunchao Liu; Junbiao Chang; Yumei Chen; Bo Wan; Yinbiao Wang; Gaiping Zhang (Biotechnology Letters, 2012)

Serum Selenium Levels in Korean Hepatoma Patients - In-Wook Kim; Su-Mi Bae; Yong-Wan Kim; Hai-Bo Liu; Si Hyun Bae; Jong Young Choi; Seung Kew Yoon; Pankaj Kumar Chaturvedi; Gantumur Battogtokh; Woong Shick Ahn (Biological Trace Element Research, 2012)

N-Nitrosodimethylamine induced lung fibroblast cell death is associated with JNK activation - Bo Li; Do-Sung Kim; Hyo-Won Oh; Hyun-Dae Lim; Wan Lee; Ki Yon Rhew; Hyung-Ryong Kim; Han-Jung Chae (Molecular & Cellular Toxicology, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Literature and patent analysis of the cloning and identification of human functional genes in China - Yan Xia; LiSha Tang; Lei Yao; Bo Wan; XianMei Yang; Long Yu (Science China Life Sciences, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Genotyping cytomegalovirus UL97 mutations by high-resolution melting analysis with unlabeled probe - Xiao-Tao Zhao; Dan-Qiu Zhou; Shuai Wu; Yue-Wen Chen; Yong Shao; Jie Zhang; Chang-Sheng Xia; Ke-Peng Wang; Hong Yang; Jun Wan; Bo Yu; Zheng Zhang; et al. (Archives of Virology, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Comparison of Bacterial and Fungal Communities Between Natural and Planted Pine Forests in Subtropical China - Ming Nie; Han Meng; Ke Li; Jia-Rong Wan; Zhe-Xue Quan; Chang-Ming Fang; Jia-Kuan Chen; Bo Li (Current Microbiology, 2012)

Hepatitis B virus X protein enhances activation of nuclear factor κB through interaction with valosin-containing protein - Bo-Yan Jiao; Wan-Song Lin; Fei-Fei She; Wan-Nan Chen; Xu Lin (Archives of Virology, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Effect of host plants on development and reproduction of Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Rui-Ting Ju; Feng Wang; Fang-Hao Wan; Bo Li (Journal of Pest Science, 2011)

Impacts of the herbicide butachlor on the larvae of a paddy field breeding frog (Fejervarya limnocharis) in subtropical Taiwan - Wan-Yi Liu; Ching-Yuh Wang; Tsu-Shing Wang; Gary M. Fellers; Bo-Chi Lai; Yeong-Choy Kam (Ecotoxicology, 2011)

A rice β-1,3-glucanase gene Osg1 is required for callose degradation in pollen development - Linglin Wan; Wenjun Zha; Xiaoyan Cheng; Chuan Liu; Lu Lv; Caixiang Liu; Zhanqi Wang; Bo Du; Rongzhi Chen; Lili Zhu; Guangcun He (Planta, 2011)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)

Re–Os and 40Ar/39Ar ages of the Jiguanshan porphyry Mo deposit, Xilamulun metallogenic belt, NE China, and constraints on mineralization events - Huaying Wu; Lianchang Zhang; Bo Wan; Zhiguang Chen; Peng Xiang; Franco Pirajno; Andao Du; Wenjun Qu (Mineralium Deposita, 2011)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

AMP-activated protein kinase supports the NGF-induced viability of human HeLa cells to glucose starvation - Luo Ting; Wan Bo; Ruwei Li; Xinya Chen; Yingli Wang; Zhou Jun; Long Yu (Molecular Biology Reports, 2010)

Genetic variations in the CεmX domain of human membrane-bound IgE - Lei Wan; Jiun-Bo Chen; Hsih Hsin Chen; Janice Huang; Hui-Ming Yu; Shue-Fen Luo; Fuu Jen Tsai; Tse Wen Chang (Immunogenetics, 2010)

Identification and characterization of human LYPD6, a new member of the Ly-6 superfamily - Yifeng Zhang; Qingyu Lang; Jie Li; Fang Xie; Bo Wan; Long Yu (Molecular Biology Reports, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

3-Hydroxyflavone inhibits endogenous Aurora B and induces growth inhibition of cancer cell line - Qingyu Lang; Haoxing Zhang; Jie Li; Fang Xie; Yifeng Zhang; Bo Wan; Long Yu (Molecular Biology Reports, 2010)

Biological impact of harmaline, ricinine and their combined effects with Bacillus thuringiensis on Spodoptera exigua (Lepidoptera: Noctuidae) - Muhammad Rizwan-ul-Haq; Qiong Bo Hu; Mei Ying Hu; Qing Shen Lin; Wan Li Zhang (Journal of Pest Science, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Cloning and characterization of a human LYPD7, a new member of the Ly-6 superfamily - Jun Ni; Qingyu Lang; Meirong Bai; Chaomin Zhong; Xinya Chen; Bo Wan; Long Yu (Molecular Biology Reports, 2009)

Identification of a novel human lactate dehydrogenase gene LDHAL6A, which activates transcriptional activities of AP1(PMA) - Xinya Chen; Xiuting Gu; Yuxi Shan; Wenwen Tang; Jian Yuan; Zhaomin Zhong; Yingli Wang; Weixue Huang; Bo Wan; Long Yu (Molecular Biology Reports, 2009)

Interaction between SARS-CoV helicase and a multifunctional cellular protein (Ddx5) revealed by yeast and mammalian cell two-hybrid systems - Jin-Yan Chen; Wan-Nan Chen; Kwok-Man Vincent Poon; Bo-Jian Zheng; Xu Lin; Yong-Xiang Wang; Yu-Mei Wen (Archives of Virology, 2009)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Cloning and characterization of a human GDPD domain-containing protein GDPD5 - Qingyu Lang; Haoxing Zhang; Jie Li; Hongkun Yin; Yifeng Zhang; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2008)

Identification of TCP10L as primate-specific gene derived via segmental duplication and homodimerization of TCP10L through the leucine zipper motif - Zhaomin Zhong; Jianping Qiu; Xinya Chen; Bo Wan; Jun Ni; Yun Yang; Meirong Bai; Haoxing Zhang; Long Yu (Molecular Biology Reports, 2008)

Characterization of Novel Orange Fluorescent Protein Cloned from Cnidarian Tube Anemone Cerianthus sp. - Denis Tsz-Ming Ip; Kam-Bo Wong; David Chi-Cheong Wan (Marine Biotechnology, 2007)

A new cytotoxic cholesterol sulfate from marine sponge Halichondria rugosa - Hong-Jun Zhang; Jing-Bo Sun; Hou-Wen Lin; Zeng-Lei Wang; Hua Tang; Ping Cheng; Wan-Sheng Chen; Yang-Hua Yi (Natural Product Research, 2007)

Cloning and characterization of the human gene RAP2C, a novel member of Ras family, which activates transcriptional activities of SRE - Zekun Guo; Jian Yuan; Wenwen Tang; Xinya Chen; Xiuting Gu; Kuntian Luo; Yingli Wang; Bo Wan; Long Yu (Molecular Biology Reports, 2007)

An invasive aster (Ageratina adenophora) invades and dominates forest understories in China: altered soil microbial communities facilitate the invader and inhibit natives - Hong-bang Niu; Wan-xue Liu; Fang-hao Wan; Bo Liu (Plant and Soil, 2007)

Efficient transient expression and transformation of PEG-mediated gene uptake into mesophyll protoplasts of pepper (Capsicum annuum L.) - Joo Mi Jeon; Nam Young Ahn; Bo Hwa Son; Cha Young Kim; Chang-deok Han; Gun-Do Kim; Sang Wan Gal; Sung-Ho Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Cloning and characterization of the human gene DERP6, which activates transcriptional activities of p53 - Jian Yuan; Wenwen Tang; Kuntian Luo; Xinya Chen; Xiuting Gu; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Cloning and Characterization of a Novel, Human Cellular Retinaldehyde-binding Protein CRALBP-like (CRALBPL) Gene - Ya-Hui Kong; Guang-Ming Ye; Kai Qu; Wen-Qi Pan; Xiang-Hua Liu; Bo Wan; Jin-Hu Guo; Long Yu (Biotechnology Letters, 2006)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Identification and Characterization of the Human SCAN Domain Zinc-Finger Gene ZNF449 - Kuntian Luo; Jie Li; Yanhui Cui; Meng Xu; Jian Yuan; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Identification and Characterization of RHEBL1, a Novel Member of Ras Family, which Activates Transcriptional Activities of NF-Kappa B - Jian Yuan; Yuxi Shan; Xinya Chen; Wenwen Tang; Kuntian Luo; Jun Ni; Bo Wan; Long Yu (Molecular Biology Reports, 2005)

GADD45γ, down-regulated in 65% Hepatocellular Carcinoma (HCC) from 23 Chinese patients, inhibits cell growth and induces cell cycle G2/M arrest for Hepatoma Hep-G2 cell lines - Luhong Sun; Ruomu Gong; Bo Wan; Xinghua Huang; Chaoqun Wu; Xirang Zhang; Shouyuan Zhao; Long Yu (Molecular Biology Reports, 2003)

Response of soil CO2 efflux to water manipulation in a tallgrass prairie ecosystem - Xiaozhong Liu; Shiqiang Wan; Bo Su; Dafeng Hui; Yiqi Luo (Plant and Soil, 2002)

Cloning of human myeloid-associated differentiation marker (MYADM) gene whose expression was up-regulated in NB4 cells induced by all-trans retinoic acid - Wanchang Cui; Long Yu; Hua He; Yaya Chu; Jie Gao; Bo Wan; Lisha Tang; Shouyuan Zhao (Molecular Biology Reports, 2001)

Identification of human, mouse and rat PPP1R14A, protein phosphatase-1 inhibitor subunit 14A, & mapping human PPP1R14A to chromosome 19q13.13-q13.2 - Zhiyi Li; Long Yu; Yazhou Zhang; Jie Gao; Pingzhao Zhang; Bo Wan; Chiyuan Chen; Shouyuan Zhao (Molecular Biology Reports, 2001)